2-Stage and 3-stage restorative proctocolectomy with ileal pouch-anal anastomosis for ulcerative colitis show comparable short- and long-term outcomes - Brunner, Maximilian; Brandl, Martin; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Weber, Klaus (Scientific Reports, 2024)
Restorative proctocolectomy with ileal pouch-anal anastomosis (IPAA) represents the standard treatment for therapy-refractory, malignant or complicated ulcerative colitis (UC) and can be performed as a 2-stage or 3-stage procedure. This study aimed to compare the short- and long-term outcomes after 2- and 3-stage IPAA in patients with UC in our department. A retrospective analysis of 176 patients with UC who received 2- or 3-stage restorative proctocolectomy with IPAA at our institution from 2001 to 2021 was performed. Outcomes for short-term (morbidity, longer hospital stay, readmission) and long-term (pouch failure and quality of life) parameters were compared between the 2- and 3-stage procedure. Regarding short-term outcomes for all patients, in-hospital morbidity and readmission rates after any surgical stage were observed in 69% and 24%, respectively. Morbidity and readmission did not differ significantly between the 2- and 3-stage procedure in uni- and multivariate analysis. Median length of hospital stay for all stages was 17 days. The 3-stage procedure was identified as an independent factor for longer hospital stay (OR 3.8 (CI 1.3-10.8), p = 0.014). Pouch failure and failure of improved quality of life during long-term follow-up occurred both in 10% of patients, with no significant differences between the 2- and 3-stage procedure in uni- and multivariate analysis. Our data suggest that both the 2- and 3-stage proctocolectomy with IPAA demonstrate favourable and comparable postoperative short- and long-term outcomes, with a high rate of improved quality of life in patients with UC.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Ileal pouch-anal anastomosis; Outcome; Pouch failure; Proctocolectomy; Ulcerative colitis

Analysis of Intraoperative Frozen Pancreatic Resection Margin and Prediction of Postoperative Pancreatic Fistula Risk During Pancreatoduodenectomy - Brunner, Maximilian; Kovacevic, Jasna; Krautz, Christian; Merkel, Susanne; Hartmann, Arndt; Grützmann, Robert; Haller, Florian; Weber, Georg (Journal of the American College of Surgeons, 2022)
BACKGROUND: Pancreatic duct diameter and pancreatic texture are important predictive factors for a postoperative pancreatic fistula (POPF) and are assessed intraoperatively by the surgeon. However, surgical evaluation is arbitrary and difficult to objectify, especially in minimally invasive approaches in pancreatic surgery. STUDY DESIGN: We conducted a retrospective analysis of 275 patients that underwent pancreatoduodenectomy from 2012 to 2019 at our institution. Pancreatic duct diameter and pancreatic fibrosis were assessed by histopathologic examination of the pancreatic resection margin using intraoperative frozen sections and correlated with the occurrence of POPF and clinically relevant POPF (CR-POPF). RESULTS: The POPF and CR-POPF rates were 27% and 19%, respectively. Univariate analysis indicated that the indication for surgery, the surgically determined pancreatic duct diameter, and pancreatic texture, as well as the histopathologically determined pancreatic duct diameter and pancreatic fibrosis were significant predictive factors for POPF and CR-POPF. A multivariate analysis revealed histopathologically determined pancreatic duct diameter and pancreatic fibrosis as independent risk factors for POPF (OR [odds ratio] 2.3 [1.1 to 4.5], p = 0.022 and OR 2.4 [1.1 to 5.1], p = 0.023, respectively) and CR-POPF (OR 2.2 [1.1 to 4.8], p = 0.037 and OR 2.6 [1.1 to 6.1], p = 0.036). CONCLUSIONS: Histopathologically determined pancreatic duct diameter and pancreatic fibrosis are quantitatively measurable independent risk factors for POPF and CR-POPF. An intraoperative objective histopathologic evaluation of these parameters using frozen sections could support the surgical assessment of the pancreatic duct diameter and the pancreatic texture.
CRIS-Team Scopus Importer:2022-04-29

A novel approach for in vivo DNA footprinting using short double-stranded cell-free DNA from plasma - Müller, Jan; Hartwig, Christina; Sonntag, Mirko; Bitzer, Lisa; Adelmann, Christopher; Vainshtein, Yevhen; Glanz, Karolina; Decker, Sebastian O.; Brenner, Thorsten; Weber, Georg; von Haeseler, Arndt; Sohn, Kai (Genome Research, 2024)
Here, we present a method for enrichment of double-stranded cfDNA with an average length of ∼40 bp from cfDNA for high-throughput DNA sequencing. This class of cfDNA is enriched at gene promoters and binding sites of transcription factors or structural DNA-binding proteins, so that a genome-wide DNA footprint is directly captured from liquid biopsies. In short double-stranded cfDNA from healthy individuals, we find significant enrichment of 203 transcription factor motifs. Additionally, short double-stranded cfDNA signals at specific genomic regions correlate negatively with DNA methylation, positively with H3K4me3 histone modifications and gene transcription. The diagnostic potential of short double-stranded cell-free DNA (cfDNA) in blood plasma has not yet been recognized. When comparing short double-stranded cfDNA from patient samples of pancreatic ductal adenocarcinoma with colorectal carcinoma or septic with postoperative controls, we identify 136 and 241 differentially enriched loci, respectively. Using these differentially enriched loci, the disease types can be clearly distinguished by principal component analysis, demonstrating the diagnostic potential of short double-stranded cfDNA signals as a new class of biomarkers for liquid biopsies.
CRIS-Team Scopus Importer:2024-10-04

An overview of proteomic methods for the study of ‘cytokine storms’ - David, Paul; Hansen, Frederik; Bhat, Adil; Weber, Georg (Expert Review of Proteomics, 2021)
Introduction: The cytokine storm is a form of excessive systemic inflammatory reaction triggered by a myriad of factors that may lead to multi-organ failure, and finally to death. The cytokine storm can occur in a number of infectious and noninfectious diseases including COVID-19, sepsis, ebola, avian influenza, and graft versus host disease, or during the severe inflammatory response syndrome. Area covered: This review mainly focuses on the most common and well-known methods of protein studies (PAGE, SDS-PAGE, and high- performance liquid chromatography). It also discusses other modern technologies in proteomics like mass spectrometry, soft ionization techniques, cytometric bead assays, and the next generation of microarrays that have been used to get an in-depth understanding of the pathomechanisms involved during the cytokine storm. Expert opinion: Overactivation of leukocytes drives the production and secretion of inflammatory cytokines fueling the cytokine storm. These events lead to a systemic hyper-inflammation, circulatory collapse and shock, and finally to multiorgan failure. Therefore, monitoring the patient’s systemic cytokine levels with proteomic technologies that are redundant, economical, and require minimal sample volume for real-time assessment might help in a better clinical evaluation and management of critically ill patients.
CRIS-Team Scopus Importer:2021-04-30
Keywords: COVID-19; Cytokine storm; immunoassays; immunotherapies; mass spectrometry; proteomic methods

Antibiotic treatment after appendectomy for acute complicated appendicitis to prevent intrabdominal abscess and wound infections - Laverde, Bruno Leonardo Bancke; Maak, Matthias; Langheinrich, Melanie; Kersting, Stephan; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Langenbecks Archives of Surgery, 2024)
Introduction: The purpose of this analysis was to investigate the most appropriate duration of postoperative antibiotic treatment to minimize the incidence of intraabdominal abscesses and wound infections in patients with complicated appendicitis. Materials and methods: In this retrospective study, which included 396 adult patients who underwent appendectomy for complicated appendicitis between January 2010 and December 2020 at the University Hospital Erlangen, patients were classified into two groups based on the duration of their postoperative antibiotic intake: ≤ 3 postoperative days (group 1) vs. ≥ 4 postoperative days (group 2). The incidence of postoperative intraabdominal abscesses and wound infections were compared between the groups. Additionally, multivariate risk factor analysis for the occurrence of intraabdominal abscesses and wound infections was performed. Results: The two groups contained 226 and 170 patients, respectively. The incidence of postoperative intraabdominal abscesses (2% vs. 3%, p = 0.507) and wound infections (3% vs. 6%, p = 0.080) did not differ significantly between the groups. Multivariate analysis revealed that an additional cecum resection (OR 5.5 (95% CI 1.4–21.5), p = 0.014) was an independent risk factor for intraabdominal abscesses. A higher BMI (OR 5.9 (95% CI 1.2–29.2), p = 0.030) and conversion to an open procedure (OR 5.2 (95% CI 1.4–20.0), p = 0.016) were identified as independent risk factors for wound infections. Conclusion: The duration of postoperative antibiotic therapy does not appear to influence the incidence of postoperative intraabdominal abscesses and wound infections. Therefore, short-term postoperative antibiotic treatment should be preferred.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Appendectomy; Complicated appendicitis; Intraabdominal abscess; Postoperative antibiotic therapy; Wound infection

BATF-dependent IL-7RhiGM-CSF+ T cells control intestinal graft-versus-host disease - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Büttner-Herold, Maike; Buchele, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (Journal of Clinical Investigation, 2018)
Acute graft-versus-host disease (GVHD) represents a severe, T cell-driven inflammatory complication following allogeneic hematopoietic cell transplantation (allo-HCT). GVHD often affects the intestine and is associated with a poor prognosis. Although frequently detectable, proinflammatory mechanisms exerted by intestinal tissue-infiltrating Th cell subsets remain to be fully elucidated. Here, we show that the Th17-defining transcription factor basic leucine zipper transcription factor ATF-like (BATF) was strongly regulated across human and mouse intestinal GVHD tissues. Studies in complete MHC-mismatched and minor histocompatibility-mismatched (miHA-mismatched) GVHD models revealed that BATF-expressing T cells were functionally indispensable for intestinal GVHD manifestation. Mechanistically, BATF controlled the formation of colon-infiltrating, IL-7 receptor-positive (IL-7R+), granulocyte-macrophage colony-stimulating factor-positive (GM-CSF+), donor T effector memory (Tem) cells. This T cell subset was sufficient to promote intestinal GVHD, while its occurrence was largely dependent on T cell-intrinsic BATF expression, required IL-7-IL-7R interaction, and was enhanced by GM-CSF. Thus, this study identifies BATF-dependent pathogenic GM-CSF+ effector T cells as critical promoters of intestinal inflammation in GVHD and hence putatively provides mechanistic insight into inflammatory processes previously assumed to be selectively Th17 drive
EVALuna2:25783

Better Therapy for Pancreatic Cancer through More Radical Surgery? Bessere Therapie des Pankreaskarzinoms durch radikalere Chirurgie? - Brunner, Maximilian; Krautz, Christian; Grützmann, Robert; Weber, Georg (Zentralblatt für Chirurgie, 2022)
Despite advances in the treatment of pancreatic cancer, the survival of affected patients remains limited. A more radical surgical therapy could help to improve the prognosis, in particular by reducing the local recurrence rate, which is around 45% in patients with resected pancreatic cancer. In addition, patients with oligometastatic pancreatic cancer could also benefit from a more radical indication for surgery.Based on an analysis of the literature, important principles of pancreatic cancer surgery were examined.Even if even more radical surgical approaches such as an "extended" lymphadenectomy or a standard complete pancreatectomy do not bring any survival advantage, complete resection of the tumour (R0), a thorough locoregional lymphadenectomy and an adequate radical dissection in the area of the peripancreatic vessels including periarterial nerve plexuses should be the standard of pancreatic carcinoma resections. Whenever necessary to achieve an R0 resection, resections of the pancreas have to be extended, as well as additional venous vascular resections and multivisceral resections had to be performed. Simultaneous arterial vascular resections as part of pancreatic resections as well as surgical resections in oligometastatic patients should, however, be reserved for selected patients. These aspects of the surgical technique in pancreatic carcinoma mentioned above must not be neglected from the point of view of an "existing limited prognosis". On the contrary, they form the absolutely necessary basis in order to achieve good survival results in combination with system therapy. However, it may always be necessary to adapt these standards according to the age, comorbidities and wishes of the patient.
CRIS-Team Scopus Importer:2022-04-15

Branch duct intraductal papillary mucinous neoplasm - contra resection - Brunner, Michaela; Kersting, S.; Grützmann, Robert; Weber, Georg (Chirurg, 2017)
Due to improvements in imaging modalities the diagnosis of branch duct intraductal papillary mucinous neoplasms (BD-IPMN) has been significantly increased in recent years. A BD-IPMN is frequently diagnosed as an incidental finding in asymptomatic patients. The optimal management of BD-IPMN is the subject of controversial discussions. Numerous studies have shown that an individualized therapeutic strategy with a follow-up observation of most BD-IPMNs is feasible and safe, considering age, comorbidities and patient preference. An accurate evaluation of BD-IPMN with a detailed anamnesis, high-resolution imaging techniques and endoscopic ultrasound is necessary. Symptomatic patients as well as patients with so-called high-risk stigmata should undergo resection. Asymptomatic patients with so-called worrisome features can either undergo surveillance or surgical resection, taking age and comorbidities into account. For BD-IPMN patients without high-risk stigmata and worrisome features and showing no symptoms, surveillance of the pancreatic lesion is the preferred approach. The high prevalence of BD-IPMN, limitations in differential diagnostics, an overestimation of the risk of malignancy due to an overrepresentation of symptomatic and suspected BD-IPMN in resected cohorts, an overestimated role of BD-IPMN as precursor lesions for pancreatic carcinoma and evidence of the safety of follow-up surveillance, underline the enormous importance of surveillance. Based on this and considering the background of a notable mortality and morbidity of pancreatic surgery, aggressive management with prophylactic surgical resection is not justified for all BD-IPMN, in particular for low-risk lesions.
EVALuna2:15288

CD71 expressing circulating neutrophils serve as a novel prognostic biomarker for metastatic spread and reduced outcome in pancreatic ductal adenocarcinoma patients - Hansen, Frederik; Mittelstädt, Anke; Clausen, Finn-Niklas; Knoedler, Samuel; Knoedler, Leonard; Klöckner, Sebastian; Kuchenreuther, Isabelle; Mazurie de Keroualin, Johanne; Arnold, Lisa-Sophie; Anthuber, Anna; Jacobsen, Anne; Merkel, Susanne; et al. (Scientific Reports, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies, presenting a persisting global health burden. Neutrophils have a double-edged role in tumor progression exhibiting both pro-tumor and anti-tumor functions. CD71, also known as transferrin receptor 1, performs a critical role in cellular iron uptake and is highly expressed on proliferating cells, and especially on activated immune cells. CD71 is known to be elevated in various types of solid cancers and is associated with poor prognosis, however, the expression of CD71 on neutrophils in PDAC and its potential clinical impact is still unknown. Therefore, we analyzed CD71 on circulating neutrophils in PDAC and clinical control patients and found a significant increased expression in PDAC patients. High expression of CD71 on neutrophils in PDAC patients was associated with reduced outcome compared to low expression. CD71 on neutrophils correlated positively with the levels of proinflammatory cytokines IL-6, IFN-γ, and growth factor ligands CD40-L, and BAFF in plasma of PDAC patients. Finally, we have demonstrated that high expression of CD71 on neutrophils was also associated with an increased expression of CD39 and CD25 on circulating T-cells. Based on our findings, we hypothesize that CD71 on neutrophils is associated with tumor progression in PDAC. Further studies are required to investigate the distinct functionality of CD71 expressing neutrophils and their potential clinical application.
CRIS-Team Scopus Importer:2024-09-20
Keywords: CD71; Metastatic spread; Neutrophils; Pancreatic ductal adenocarcinoma; Prognostic biomarker; Transferrin receptor 1

Cinematic Rendering in Anatomy: A Crossover Study Comparing a Novel 3D Reconstruction Technique to Conventional Computed Tomography - Binder, Johannes; Scholz, Michael; Ellmann, Stephan; Uder, Michael; Grützmann, Robert; Krautz, Christian; Weber, Georg (Anatomical Sciences Education, 2020)
Integration of medical imaging into preclinical anatomy courses is already underway in many medical schools. However, interpretation of two-dimensional grayscale images is difficult and conventional volume rendering techniques provide only images of limited quality. In this regard, a more photorealistic visualization provided by Cinematic Rendering (CR) may be more suitable for anatomical education. A randomized, two-period crossover study was conducted from July to December 2018, at the University Hospital of Erlangen, Germany to compare CR and conventional computed tomography (CT) imaging for speed and comprehension of anatomy. Sixteen students were randomized into two assessment sequences. During each assessment period, participants had to answer 15 anatomy-related questions that were divided into three categories: parenchymal, musculoskeletal, and vascular anatomy. After a washout period of 14 days, assessments were crossed over to the respective second reconstruction technique. The mean interperiod differences for the time to answer differed significantly between the CR-CT sequence (-204.21 +/- 156.0 seconds) and the CT-CR sequence (243.33 +/- 113.83 seconds;P < 0.001). Overall time reduction by CR was 65.56%. Cinematic Rendering visualization of musculoskeletal and vascular anatomy was higher rated compared to CT visualization (P P = 0.003), whereas CT visualization of parenchymal anatomy received a higher scoring than CR visualization (P < 0.001). No carryover effects were observed. A questionnaire revealed that students consider CR to be beneficial for medical education. These results suggest that CR has a potential to enhance knowledge acquisition and transfer from medical imaging data in medical education.
CRIS-Team WoS Importer:2020-07-17

Circulating Monocytes Serve as Novel Prognostic Biomarker in Pancreatic Ductal Adenocarcinoma Patients - Hansen, Frederik; David, Paul; Akram, Marina; Knoedler, Samuel; Mittelstädt, Anke; Merkel, Susanne; Podolska, Malgorzata; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; Kouhestani, Dina; Anthuber, Anna; et al. (Cancers, 2023)
Pancreatic ductal adenocarcinoma (PDAC) ranks among the most fatal cancer diseases, widely accepted to have the most dismal prognoses. Although immunotherapy has broadly revolutionized cancer treatment, its value in PDAC appears to be relatively low. Exhibiting protumoral effects, monocytes have recently been proposed as potential targets of such immunotherapeutic regimens. However, to date, the body of evidence on monocytes’ role in PDAC is scarce. Therefore, we analyzed monocytes in the peripheral blood of 58 PDAC patients prior to surgery and compared them to healthy individuals. PDAC patients showed increased levels of monocytes when compared to healthy controls In addition, patients with perineural infiltration demonstrated a higher percentage of monocytes compared to non-infiltrating tumors and PDAC G3 was associated with higher monocyte levels than PDAC G2. Patients with monocyte levels > 5% were found to have an 8.9-fold increased risk for a G3 and perineural infiltrated PDAC resulting in poorer survival compared to patients with <5% monocyte levels. Furthermore, PDAC patients showed increased expressions of CD86 and CD11c and decreased expressions of PD-L1 on monocytes compared to healthy individuals. Finally, levels of monocytes correlated positively with concentrations of IL-6 and TNF-α in plasma of PDAC patients. Based on our findings, we propose monocytes as a novel prognostic biomarker. Large-scale studies are needed to further decipher the role of monocytes in PDAC and investigate their potential as therapeutic targets.
CRIS-Team Scopus Importer:2023-02-03
Keywords: grading; liquid biopsy; monocytes; pancreatic ductal adenocarcinoma; perineural invasion; prognostic biomarker

Colorectal cancer in Crohn’s colitis is associated with advanced tumor invasion and a poorer survival compared with ulcerative colitis: a retrospective dual-center study - Vetter, Leonie E.; Merkel, Susanne; Bénard, Alan; Krautz, Christian; Brunner, Maximilian; Mittelstädt, Anke; Schlegel, Nicolas; Wiegering, Armin; Germer, Christoph Thomas; Weber, Klaus; Grützmann, Robert; Weber, Georg (International Journal of Colorectal Disease, 2020)
Purpose: Colorectal cancer is a well-recognized complication of inflammatory bowel diseases (IBD), such as ulcerative colitis (UC) and Crohn’s colitis (CC). In this study, we assess the clinico-pathological features and outcomes of patients with colorectal cancer from UC in comparison with CC. Methods: Data of all patients with colitis-associated cancer (CAC) who underwent surgery at Erlangen or Würzburg University Clinic between 1995 and 2015 were selected. Clinical, histopathological, and survival data were analyzed retrospectively. Results: Of all 88 patients with CAC, 20 patients had Crohn’s colitis and 68 patients had ulcerative colitis. We observed a young median age at tumor diagnosis (49.5 years UC; 45.5 years CC, p = 0.208) in both diseases and a long median disease duration before CAC (19 years UC; 18 years CC; p = 0.840). Patients with CC suffered more often from rectal cancer (14 (70.0%) in CC; 23 (33.8%) in UC; p = 0.005) and advanced tumor stages (8 (47.0%) pT4 in CC; 14 (25.0%) pT4/ypT4 in UC; p = 0.008). Five-year overall survival rate was 39.3% for CC and 67.1% for UC (p = 0.009 for difference between the groups). Survival did not differ significantly between UC and CC in the multivariate analysis after correction for UICC tumor stage. Conclusion: CAC in CC showed advanced tumor stages associated with reduced survival compared with CAC in UC. This may be explained by less intense surveillance in patients with CC leading to delayed cancer diagnosis.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Colorectal cancer; Crohn’s colitis; Ulcerative colitis

Comparison of Cinematic Rendering and Computed Tomography for Speed and Comprehension of Surgical Anatomy - Elshafei, Moustafa; Binder, Johannes; Baecker, Justus; Brunner, Maximilian; Uder, Michael; Grützmann, Robert; Krautz, Christian; Weber, Georg (JAMA Surgery, 2019)
Importance: Three-dimensional (3-D) volume rendering has been shown to improve visualization in general surgery. Cinematic rendering (CR), a novel 3-D visualization technology for postprocessing of computed tomographaphy (CT) images, provides photorealistic images with the potential to improve visualization of anatomic details. Objective: To determine the value of CR for the comprehension of the surgical anatomy. Design, Setting, and Participants: This preclinical, randomized, 2-sequence crossover study was conducted from February to November 1, 2018, at University Hospital of Erlangen, Germany. The 40 patient cases were evaluated by 18 resident and attending surgeons using a prepared set of CT and CR images. The patient cases were randomized to 2 assessment sequences (CR-CT and CT-CR). During each assessment period, participants answered 1 question per case that addressed crucial issues of anatomic understanding, preoperative planning, and intraoperative strategies. After a washout period of 2 weeks, case evaluations were crossed over to the respective second image modality. Main Outcomes and Measures: The primary outcome measure was the correctness of answers. Secondary outcome was the time needed to answer. Results: The mean (SD) interperiod differences for the percentage of correct answers in the CR-CT sequence (8.5% [7.0%]) differed significantly from those in the CT-CR sequence (-13.1% [6.3%]) (P <.001). The mean (SD) interperiod differences for the time spent to answer the questions in the CR-CT sequence (-18.3 [76.9] seconds) also differed significantly from those in the CT-CR sequence (52.4 [88.5] seconds) (P <.001). Subgroup analysis revealed that residents as well as attending physicians benefitted from CR visualization. Analysis of the case assessment questionnaire showed that CR added significant value to the comprehension of the surgical anatomy (overall mean [SD] score, 4.53 [0.75]). No carryover or period effects were observed. Conclusions and Relevance: The visualization with CR allowed a more correct and faster comprehension of the surgical anatomy compared with conventional CT imaging, independent of level of surgeon experience. Therefore, CR may assist general surgeons with preoperative preparation and intraoperative guidance..
CRIS-Team Scopus Importer:2019-06-18

Continuous or Interrupted Suture for Hepaticojejunostomy in Pancreaticoduodenectomy (The HEKTIK Trial): Findings of a Randomized, Controlled, Single-Center Superiority Trial. - Brunner, Maximilian; Golcher, Henriette; Krautz, Christian; Kersting, Stephan; Weber, Georg; Grützmann, Robert (Deutsches Ärzteblatt international, 2024)
BACKGROUND: Over 6000 pancreaticoduodenectomies are per - formed each year in Germany, and hepaticojejunostomy is a crucial step of the procedure. An anastomotic leak of hepaticojejunostomy can cause major postoperative complications. The aim of this trial was to compare the morbidity and efficiency of continuous versus interrupted suturing for hepaticojejunostomy in pancreaticoduo - denectomy. METHODS: In a randomized, controlled, single-center trial (German Clinical Trials Register No. DRKS00024395), patients scheduled for elective open partial pancreaticoduodenectomy with hepaticoje - junostomy between January 2020 and May 2023 were randomly assigned in a 1:1 ratio to suturing of the hepaticojejunostomy with either a continuous or an interrupted technique. The primary endpoint was anastomotic leakage from the hepaticojejunostomy in the first three days after surgery. Further perioperative parameters were secondary endpoints, including later leakage, other complications, the duration of hepaticojejunostomy, and the cost of hepaticojejunostomy. RESULTS: The 100 patients in the trial consisted of 50 in each group. The rate of early anastomotic leakage was 2% in both groups (95% confidence interval for the difference, [-5.5%; 5.5%]; p = 1.000). As for the secondary endpoints, there were no relevant intergroup differences in any other short-term or long-term morbidity parameters. Continuous suturing of the hepaticojejunostomy was, however, 31% faster and 68% cheaper in material costs. CONCLUSION: These data imply that continuous and interrupted suturing techniques yield equally good clinical outcomes in hepaticojejunostomies of hepatic ducts with diameter 5 mm or more. Continuous suturing is, however, both faster and cheaper.
EVALuna2:583241

Continuous or interrupted suture technique for hepaticojejunostomy? A national survey - Brunner, Maximilian; Stockheim, Jessica; Krautz, Christian; Raptis, Dimitrios; Kersting, Stephan; Grützmann, Robert; Weber, Georg (BMC Surgery, 2018)
BACKGROUND: Hepaticojejunostomy is commonly used in hepato-bilio-pancreatic surgery and a crucial step in many surgical procedures, including pancreaticoduodenectomy. The most frequently used techniques are the interrupted suture and the continuous suture technique. Currently, there is no data available in regard to the utilization of these techniques. METHODS: In total, 102 hospitals in Germany were invited between September and November 2017 to participate in this survey. Using a paper-based questionnaire, data were collected on surgical technique and complication rates of hepaticojejunostomies. RESULTS: A total of 77 of the 102 addressed hospitals (76%) participated in the survey. On average, each hospital performed 71 hepaticojejunostomies per year - most often in the context of pancreaticoduodenectomy (71%). 24 (31%) hospitals exclusively use an interrupted suture technique, 7 (9%) hospitals solely a continuous suture technique, 3 (4%) hospitals perform a combination of continuous and interrupted suture technique and 43 (56%) hospitals decide on one of both techniques depending on intraoperative findings. According to the participants in this survey, the continuous suture technique is significantly faster than the interrupted suture technique in hepaticojejunostomy (p = 0,015). There were no significant differences in the overall complication rate (p = 0,902) and insufficiency rate (p = 1,000). CONCLUSIONS: In Germany, there is a heterogeneity in the technique used to create a hepaticojejunostomy. As our survey suggests that the use of continuous suture technique may offer an advantage in time without jeopardizing patient outcomes, the different techniques should be compared in a randomized controlled study.
EVALuna2:210706

Continuous or interrupted suture technique for hepaticojejunostomy during pancreatoduodenectomy (HEKTIK trial): study protocol of a randomized controlled multicenter trial - Brunner, Maximilian; Golcher, Henriette; Krautz, Christian; Kersting, Stephan; Grützmann, Robert; Weber, Georg (Trials, 2022)
Background: Hepaticojejunostomy is commonly performed in hepato-bilio-pancreatic surgery, particularly during pancreaticoduodenectomy. The purpose of this study is to evaluate the safety and efficiency of two commonly applied suture techniques (the interrupted versus the continuous suture technique) in patients undergoing a hepaticojejunostomy during pancreatoduodenectomy.
CRIS-Team WoS Importer:2022-06-24

Current Applications of Liquid Biopsy in Gastrointestinal Cancer Disease—From Early Cancer Detection to Individualized Cancer Treatment - David, Paul; Mittelstädt, Anke; Kouhestani, Dina; Anthuber, Anna; Kahlert, Christoph; Sohn, Kai; Weber, Georg (Cancers, 2023)
Worldwide, gastrointestinal (GI) cancers account for a significant amount of cancer-related mortality. Tests that allow an early diagnosis could lead to an improvement in patient survival. Liquid biopsies (LBs) due to their non-invasive nature as well as low risk are the current focus of cancer research and could be a promising tool for early cancer detection. LB involves the sampling of any biological fluid (e.g., blood, urine, saliva) to enrich and analyze the tumor’s biological material. LBs can detect tumor-associated components such as circulating tumor DNA (ctDNA), extracellular vesicles (EVs), and circulating tumor cells (CTCs). These components can reflect the status of the disease and can facilitate clinical decisions. LBs offer a unique and new way to assess cancers at all stages of treatment, from cancer screenings to prognosis to management of multidisciplinary therapies. In this review, we will provide insights into the current status of the various types of LBs enabling early detection and monitoring of GI cancers and their use in in vitro diagnostics.
CRIS-Team Scopus Importer:2023-04-28
Keywords: circulating tumor cells (CTCs); circulating tumor DNA (ctDNA); gastrointestinal cancer; liquid biopsy; organoids; tumor exosomes; tumor-educated blood platelets (TEPs)

Current Clinical Strategies of Pancreatic Cancer Treatment and Open Molecular Questions - Brunner, Maximilian; Wu, Zhiyuan; Krautz, Christian; Pilarsky, Christian; Grützmann, Robert; Weber, Georg (International Journal of Molecular Sciences, 2019)
Pancreatic cancer is one of the most lethal malignancies and is associated with a poor prognosis. Surgery is considered the only potential curative treatment for pancreatic cancer, followed by adjuvant chemotherapy, but surgery is reserved for the minority of patients with non-metastatic resectable tumors. In the future, neoadjuvant treatment strategies based on molecular testing of tumor biopsies may increase the amount of patients becoming eligible for surgery. In the context of non-metastatic disease, patients with resectable or borderline resectable pancreatic carcinoma might benefit from neoadjuvant chemo- or chemoradiotherapy followed by surgeryPatients with locally advanced or (oligo-/poly-)metastatic tumors presenting significant response to (neoadjuvant) chemotherapy should undergo surgery if R0 resection seems to be achievable. New immunotherapeutic strategies to induce potent immune response to the tumors and investigation in molecular mechanisms driving tumorigenesis of pancreatic cancer may provide novel therapeutic opportunities in patients with pancreatic carcinoma and help patient selection for optimal treatment.
CRIS-Team Scopus Importer:2019-10-01
Keywords: chemoradiation; chemotherapy; immunotherapy; molecular mechanism; pancreatic cancer; surgery; therapeutic targets; treatment options

Cytokine storm and sepsis disease pathogenesis - Chousterman, Benjamin G.; Swirski, Filip K.; Weber, Georg (Seminars in Immunopathology, 2017)
Infectious diseases are a leading cause of death worldwide. Sepsis is a severe clinical syndrome related to the host response to infection. The severity of infections is due to an activation cascade that will lead to an autoamplifying cytokine production: the cytokine storm. Cytokines are a broad category of relatively small proteins (<40 kDa) that are produced and released with the aim of cell signaling. Our understanding of the processes that trigger this tremendous amount of cytokine production has made dramatic progress over the last decades, but unfortunately, these findings could not translate yet into effective treatments; so far, all clinical trials targeting cytokine production or effects failed. This review aims to summarize the pathophysiology of the cytokine storm; to describe the type, effects, and kinetics of cytokine production; and to discuss the therapeutic challenges of targeting cytokines. New promising therapeutic strategies focusing on the endothelium, as a source and a target of cytokines, are described.
EVALuna2:15318

Defining early recurrence in patients with resected primary colorectal carcinoma and its respective risk factors - Wiesmüller, Felix; Schuetz, Rolf; Langheinrich, Melanie; Brunner, Maximilian; Grützmann, Robert; Merkel, Susanne; Krautz, Christian; Weber, Georg (International Journal of Colorectal Disease, 2021)
Purpose: There is no evidence-based definition of early recurrence following resection of colorectal cancer. The purpose of this study is to define a point that discriminates between early and late recurrence in patients who have undergone colorectal cancer resection with curative intent and to analyze associated risk factors. Methods: A retrospective single-center cohort study was performed at a university hospital recognized as a comprehensive cancer center, specializing in colorectal cancer surgery. Patient data were retrieved from a prospectively maintained institutional database. Included patients underwent resection for primary, non-metastatic colorectal carcinomas with curative intent between 1995 and 2010. Aims of the study were (1) to define the optimal cut-off point of recurrence-free survival based on overall survival using a minimum p value approach and (2) to identify patterns of initial recurrence and putative risk factors for early recurrence using regression models. Results: Recurrence was diagnosed in 412 of 1893 patients. Statistical analysis suggested that a recurrence-free survival of 16 months could be used to distinguish between early and late recurrence based on overall survival (p < 0.001). Independent risk factors for early recurrence included advanced pT categories (pT3,4/ypT3,4) and positive lymph node status (pN+/ypN+). Early recurrence was independent of site of recurrence and was associated with worse prognosis. Conclusions: Recurrence of colorectal carcinoma within 16 months after primary treatment should be labeled as “early.” Tumor categories pT3,4/ypT3,4 and positive lymph node status pN+/ypN+ are predictive of early recurrence.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Cancer recurrence; Colorectal cancer; Colorectal carcinoma; Follow-up; Hemicolectomy; Low anterior resection; Recurrence group

Discrimination of pancreato-biliary cancer and pancreatitis patients by non-invasive liquid biopsy - Hartwig, Christina; Müller, Jan; Klett, Hagen; Kouhestani, Dina; Mittelstädt, Anke; Anthuber, Anna; David, Paul; Brunner, Maximilian; Jacobsen, Anne; Glanz, Karolina; Swierzy, Izabela; Roßdeutsch, Lotta; et al. (Molecular Cancer, 2024)
Background: Current diagnostics for the detection of pancreato-biliary cancers (PBCs) need to be optimized. We therefore propose that methylated cell-free DNA (cfDNA) derived from non-invasive liquid biopsies serves as a novel biomarker with the ability to discriminate pancreato-biliary cancers from non-cancer pancreatitis patients. Methods: Differentially methylated regions (DMRs) from plasma cfDNA between PBCs, pancreatitis and clinical control samples conditions were identified by next-generation sequencing after enrichment using methyl-binding domains and database searches to generate a discriminatory panel for a hybridization and capture assay with subsequent targeted high throughput sequencing. Results: The hybridization and capture panel, covering around 74 kb in total, was applied to sequence a cohort of 25 PBCs, 25 pancreatitis patients, 25 clinical controls, and seven cases of Intraductal Papillary Mucinous Neoplasia (IPMN). An unbiased machine learning approach identified the 50 most discriminatory methylation markers for the discrimination of PBC from pancreatitis and controls resulting in an AUROC of 0.85 and 0.88 for a training (n = 45) and a validation (n = 37) data set, respectively. The panel was also able to distinguish high grade from low grade IPMN samples. Conclusions: We present a proof of concept for a methylation biomarker panel with better performance and improved discriminatory power than the current clinical marker CA19-9 for the discrimination of pancreato-biliary cancers from non-cancerous pancreatitis patients and clinical controls. This workflow might be used in future diagnostics for the detection of precancerous lesions, e.g. the identification of high grade IPMNs vs. low grade IPMNs.
CRIS-Team Scopus Importer:2024-02-16
Keywords: cfDNA; cfMBD-Seq; DMRs; Hybridization and capture; IPMN; Methylation; Next-generation sequencing; Non-invasive diagnostics; Pancreatitis; Pancreato-biliary cancer

Effect of Circular Stapler Diameter on Anastomotic Leakage Rate and Stenosis After Open Total Gastrectomy With Esophagojejunostomy: A Substantive Retrospective Propensity Score Matched Series. - Mittelstädt, Anke; Reitberger, Helena; Fleischmann, Julia; Elshafei, Moustafa; Brunner, Maximilian; Anthuber, Anna; Krautz, Christian; Lucio, Marianna; Merkel, Susanne; Grützmann, Robert; Weber, Georg (Annals of Surgery Open, 2022)
BACKGROUND: Anastomotic leakage (AL) and stenosis (AS) are two of the most severe postoperative complications after total gastrectomy with esophagojejunostomy. The stapler diameter can be chosen by the surgeon. Therefore, this study aims to assess the correlation between the stapler size as main independent variable as well as other different risk factors and AL and AS. METHODS: We conducted a retrospective analysis of data from 356 patients who underwent open total gastrectomy between 2000 and 2018, mostly due to gastric cancer (96.9%). After propensity score matching the outcome parameters AL and AS were compared between the two stapler size groups. We also assessed different risk factors for AL and AS in cancer patients using multivariate analysis. RESULTS: Small circular stapler diameter (21/25 mm; n = 147 vs 28/29/31 mm; n = 209) was identified as a significant risk factor for the occurrence of AL (10% vs 4% for smaller vs larger staplers; P = 0.042). In multivariate analysis for the occurrence of AL an ASA score ≥ 3 could be identified as a risk factor (OR 2.85; 95% CI = 1.13-7.15; P = 0.026). Additionally, smaller stapler size could be identified as a risk factor for AS (OR small 1.00, OR large 0.24; 95% CI: 0.06-0.97; P = 0.045). AL was associated with lower survival (18.1 vs 38.16 months; P = 0.0119). CONCLUSION: The application of a larger circular stapler for esophagojejunostomy in open total gastrectomy shows significantly lower rates of AL and stenosis. Therefore, the largest possible stapler diameter should be applied.
EVALuna2:547490

Effect of Hospital Volume on In-hospital Morbidity and Mortality Following Pancreatic Surgery in Germany - Krautz, Christian; Nimptsch, Ulrike; Mansky, Thomas; Grützmann, Robert; Weber, Georg (Annals of Surgery, 2017)
We aimed to determine the effect of hospital volume on in-hospital mortality, and failure to rescue following major pancreatic resections using hospital discharge data of every inpatient case in Germany.Several studies have found strong volume-outcome relationships in pancreatic surgery, with high mortality in low-volume facilities. However, their datasets were only based on portions of national populations. In addition, these studies did not assess the effect of hospital volume according to other crucial variables such as medical indications, postoperative complications, and failure to rescue.We studied all inpatient cases of major pancreatic surgery (n = 60,858) in Germany from 2009 to 2014, using national hospital discharge data. We evaluated the association between hospital volume and in-hospital mortality following major pancreatic resections by using multivariate regression methods. In addition, we analyzed rates of major complications and failure to rescue across hospital volume quintiles.Risk-adjusted in-hospital mortality varied widely across hospital volume quintiles, from 6.5% (95% CI 6.0-7.0) in very high volume hospitals to 11.5% (95% CI 10.9-12.1) in very low volume hospitals (OR 0.47, 95% CI 0.41-0.54). Rates of postoperative interventions necessary for complications and failure to rescue were lower in higher volume hospitals [eg, mortality following septic complications in very high volume hospitals: 24.2% (95% CI 22.4-26.1) vs. very low volume hospitals: 36.8% (34.9-38.7)]. Moreover, we estimated that centralization of surgical care to the minimum volume and mortality risk of the medium volume quintile could prevent at least 94 deaths per year.In Germany, patients who are undergoing major pancreatic resections have improved outcomes if they are admitted to higher volume hospitals. As current health policies failed to centralize pancreatic surgery procedures in Germany, new strategies to initiate a sufficient centralization process in the field of pancreatic surgery are needed.
EVALuna2:15282

Electrochemiluminescence in paired signal electrode (ECLipse) enables modular and scalable biosensing - Cho, Young Kwan; Kim, Hyunho; Benard, Alan; Woo, Hyun Kyung; Czubayko, Franziska; David, Paul; Hansen, Frederik; Lee, Jong Ik; Park, Jay Hoon; Schneck, Emmanuel; Weber, Georg; Shin, Ik Soo; et al. (Science Advances, 2022)
Electrochemiluminescence (ECL) has an inherently low background and enables precise chemical reactions through electrical control. Here, we report an advanced ECL system, termed ECLipse (ECL in paired signal electrode). We physically separated ECL generation from target detection: These two processes were carried out in isolated chambers and coupled through an electrode. The strategy allowed us to minimize cross-chemical reactions, design electrodes for high ECL signals, and integrate multiple sensors in a chip. As a proof of concept, we implemented an eight-plex ECLipse and applied it to detect host factors in human plasma. ECLipse achieved higher signal-to-noise ratio than conventional ECL assays and was >7000-fold more sensitive than enzyme-linked immunosorbent assay. In a pilot clinical study, we could detect septic conditions by measuring host factors [i.e., interleukin-3 (IL-3), IL-6, and procalcitonin (PCT)]. ECLipse assay further revealed distinct IL-3 and IL-6 patterns in patients with severe acute respiratory syndrome coronavirus 2 infection.
CRIS-Team Scopus Importer:2022-09-30

Exosomal ROR1 in peritoneal fluid identifies peritoneal disseminated PDAC and is associated with poor survival - Mittelstädt, Anke; Anthuber, Anna; David, Paul; Podolska, Malgorzata; Benard, Alan; Brunner, Maximilian; Krautz, Christian; Jacobsen, Anne; Denz, Axel; Weber, Klaus; Merkel, Susanne; Hackner, Danilo; et al. (Frontiers in Immunology, 2024)
Background: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest forms of cancer and peritoneal dissemination is one major cause for this poor prognosis. Exosomes have emerged as promising biomarkers for gastrointestinal cancers and can be found in all kinds of bodily fluids, also in peritoneal fluid (PF). This is a unique sample due to its closeness to gastrointestinal malignancies. The receptor tyrosine kinase-like orphan receptor 1 (ROR1) has been identified as a potential biomarker in human cancers and represents a promising target for an immunotherapy approach, which could be considered for future treatment strategies. Here we prospectively analyzed the exosomal surface protein ROR1 (exo-ROR1) in PF in localized PDAC patients (PER-) on the one hand and peritoneal disseminated tumor stages (PER+) on the other hand followed by the correlation of exo-ROR1 with clinical-pathological parameters. Methods: Exosomes were isolated from PF and plasma samples of non-cancerous (NC) (n = 15), chronic pancreatitis (CP) (n = 4), localized PDAC (PER-) (n = 18) and peritoneal disseminated PDAC (PER+) (n = 9) patients and the surface protein ROR1 was detected via FACS analysis. Additionally, soluble ROR1 in PF was analyzed. ROR1 expression in tissue was investigated using western blots (WB), qPCR, and immunohistochemistry (IHC). Exosome isolation was proven by Nano Tracking Analysis (NTA), WB, Transmission electron microscopy (TEM), and BCA protein assay. The results were correlated with clinical data and survival analysis was performed. Results: PDAC (PER+) patients have the highest exo-ROR1 values in PF and can be discriminated from NC (p <0.0001), PDAC (PER-) (p <0.0001), and CP (p = 0.0112). PDAC (PER-) can be discriminated from NC (p = 0.0003). In plasma, exo-ROR1 is not able to distinguish between the groups. While there is no expression of ROR1 in the exocrine pancreatic tissue, PDAC and peritoneal metastasis show expression of ROR1. High exo-ROR1 expression in PF is associated with lower overall survival (p = 0.0482). Conclusion: With exo-ROR1 in PF we found a promising diagnostic and prognostic biomarker possibly discriminating between NC, PDAC (PER-) and PDAC (PER+) and might shed light on future diagnostic and therapeutic concepts in PDAC.
CRIS-Team Scopus Importer:2024-06-14
Keywords: biomarker; exosomes; PDAC; peritoneal carcinomatosis; peritoneal fluid; peritoneal lavage; ROR1; targeted therapy

Four-and-a-Half LIM-Domain Protein 2 (FHL2) Induces Neuropeptide Y (NPY) in Macrophages in Visceral Adipose Tissue and Promotes Diet-Induced Obesity - Sommer, Judith; Ehnis, Hanna; Seitz, Tatjana; Schneider, Julia; Wild, Andreas; Moceri, Sandra; Buechler, Christa; Bozec, Aline; Weber, Georg; Merkel, Susanne; Beckervordersandforth, Ruth; Steinkasserer, Alexander; et al. (International Journal of Molecular Sciences, 2023)
Obesity is characterized by the expansion of the adipose tissue, usually accompanied by inflammation, with a prominent role of macrophages infiltrating the visceral adipose tissue (VAT). This chronic inflammation is a major driver of obesity-associated comorbidities. Four-and-a-half LIM-domain protein 2 (FHL2) is a multifunctional adaptor protein that is involved in the regulation of various biological functions and the maintenance of the homeostasis of different tissues. In this study, we aimed to gain new insights into the expression and functional role of FHL2 in VAT in diet-induced obesity. We found enhanced FHL2 expression in the VAT of mice with Western-type diet (WTD)-induced obesity and obese humans and identified macrophages as the cellular source of enhanced FHL2 expression in VAT. In mice with FHL2 deficiency (FHL2KO), WTD feeding resulted in reduced body weight gain paralleled by enhanced energy expenditure and uncoupling protein 1 (UCP1) expression, indicative of activated thermogenesis. In human VAT, FHL2 was inversely correlated with UCP1 expression. Furthermore, macrophage infiltration and the expression of the chemokine MCP-1, a known promotor of macrophage accumulation, was significantly reduced in WTD-fed FHL2KO mice compared with wild-type (wt) littermates. While FHL2 depletion did not affect the differentiation or lipid metabolism of adipocytes in vitro, FHL2 depletion in macrophages resulted in reduced expressions of MCP-1 and the neuropeptide Y (NPY). Furthermore, WTD-fed FHL2KO mice showed reduced NPY expression in VAT compared with wt littermates, and NPY expression was enhanced in VAT resident macrophages of obese individuals. Stimulation with recombinant NPY induced not only UCP1 expression and lipid accumulation but also MCP-1 expression in adipocytes. Collectively, these findings indicate that FHL2 is a positive regulator of NPY and MCP-1 expression in macrophages and herewith closely linked to the mechanism of obesity-associated lipid accumulation and inflammation in VAT. Thus, FHL2 appears as a potential novel target to interfere with the macrophage–adipocyte crosstalk in VAT for treating obesity and related metabolic disorders.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adipocytes; FHL2; macrophages; MCP-1; NPY; obesity; thermogenesis

Fra-2 regulates B cell development by enhancing IRF4 and Foxo1 transcription - Ubieta, Kenia; Garcia, Mireia; Groetsch, Bettina; Uebe, Steffen; Stein, Merle; Ekici, Arif Bülent; Schett, Georg; Mielenz, Dirk; Bozec, Aline; Weber, Georg (Journal of Experimental Medicine, 2017)
The role of AP-1 transcription factors in early B cell development and function is still incompletely characterized. Here we address the role of Fra-2 in B cell differentiation. Deletion of Fra-2 leads to impaired B cell proliferation in the bone marrow. In addition, IL-7-stimulated pro-B cell cultures revealed a reduced differentiation from large pre-B cells to small B cells and immature B cells. Gene profiling and chromatin immunoprecipitation sequencing analyses unraveled a transcriptional reduction of the transcription factors Foxo1, Irf4, Ikaros, and Aiolos in Fra-2-deficient B cells. Moreover, expression of IL7R? and Rag 1/2, downstream targets of Irf4 and Foxo1, were also reduced in the absence of Fra-2. Pro-B cell proliferation and small pre-B cell differentiation were fully rescued by expression of Foxo1 and Irf4 in Fra-2-deficient pro-B cells. Hence, Fra-2 is a key upstream regulator of Foxo1 and Irf4 expression and influences proliferation and differentiation of B cells at multiple stages.
EVALuna2:9366

Gata6+ Pericardial Cavity Macrophages Relocate to the Injured Heart and Prevent Cardiac Fibrosis - Deniset, Justin F.; Belke, Darrell; Lee, Woo Yong; Jorch, Selina K.; Deppermann, Carsten; Hassanabad, Ali Fatehi; Turnbull, Jeannine D.; Teng, G.; Rozich, Isaiah; Hudspeth, K.; Kanno, Yuka; Brooks, Stephen R.; et al. (Immunity, 2019)
Macrophages play an important role in structural cardiac remodeling and the transition to heart failure following myocardial infarction (MI). Previous research has focused on the impact of blood-derived monocytes on cardiac repair. Here we examined the contribution of resident cavity macrophages located in the pericardial space adjacent to the site of injury. We found that disruption of the pericardial cavity accelerated maladaptive post-MI cardiac remodeling. Gata6+ macrophages in mouse pericardial fluid contributed to the reparative immune response. Following experimental MI, these macrophages invaded the epicardium and lost Gata6 expression but continued to perform anti-fibrotic functions. Loss of this specialized macrophage population enhanced interstitial fibrosis after ischemic injury. Gata6+ macrophages were present in human pericardial fluid, supporting the notion that this reparative function is relevant in human disease. Our findings uncover an immune cardioprotective role for the pericardial tissue compartment and argue for the reevaluation of surgical procedures that remove the pericardium. Deniset et al. describe the pericardial cavity as an important source of resident macrophages that migrate into the heart following ischemic injury and prevent detrimental repair caused by excessive fibrosis.
CRIS-Team Scopus Importer:2019-07-09
Keywords: fibrosis; myocardial infarction; Pericardial macrophage

IL-3 orchestrates ulcerative colitis pathogenesis by controlling the development and the recruitment of splenic reservoir neutrophils - Benard, Alan; Mittelstädt, Anke; Klösch, Bettina; Glanz, Karolina; Müller, Jan; Schoen, Janina; Nüse, Björn; Brunner, Maximilian; Naschberger, Elisabeth; Stürzl, Michael; Mattner, Jochen; Munoz, Luis Enrique; et al. (Cell Reports, 2023)
Inflammatory bowel diseases (IBDs) are a global health issue with an increasing incidence. Although the pathogenesis of IBDs has been investigated intensively, the etiology of IBDs remains enigmatic. Here, we report that interleukin-3 (Il-3)-deficient mice are more susceptible and exhibit increased intestinal inflammation during the early stage of experimental colitis. IL-3 is locally expressed in the colon by cells harboring a mesenchymal stem cell phenotype and protects by promoting the early recruitment of splenic neutrophils with high microbicidal capability into the colon. Mechanistically, IL-3-dependent neutrophil recruitment involves CCL5+ PD-1high LAG-3high T cells, STAT5, and CCL20 and is sustained by extramedullary splenic hematopoiesis. During acute colitis, Il-3−/− show, however, increased resistance to the disease as well as reduced intestinal inflammation. Altogether, this study deepens our understanding of IBD pathogenesis, identifies IL-3 as an orchestrator of intestinal inflammation, and reveals the spleen as an emergency reservoir for neutrophils during colonic inflammation.
CRIS-Team Scopus Importer:2023-06-23
Keywords: CCL5; colitis; CP: Immunology; interleukin-3; neutrophils; spleen

IL-3 protects from colitis by recruiting splenic reservoir neutrophils - Benard, A.; Kloesch, B.; Kutschick, I.; Grützmann, Robert; Weber, Georg (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-05

Impact of Aspirin Intake on Postoperative Survival after Primary Pancreatic Resection of Pancreatic Ductal Adenocarcinoma—A Single-Center Evaluation - Hackner, Danilo; Hobbs, Mirianna; Merkel, Susanne; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Biomedicines, 2023)
(1) Background: The intake of aspirin (ASS) has been demonstrated to have a relevant impact on the pathogenesis, incidence and outcome in different solid gastrointestinal tumors. However, data on the effect of ASS on the short-term outcome and the long-term survival in patients with pancreatic carcinoma are still limited. (2) Methods: A total of 213 patients who underwent primary resection of PDAC at the University Hospital of Erlangen from January 2000 to December 2018 were included in this retrospective single-center study in total. Patients were stratified according to the aspirin intake into three groups: continuous aspirin intake (cASS), perioperatively interrupted aspirin intake (iASS) and no aspirin intake (no ASS) at the timepoint of surgery. The postoperative outcome as well as long-term survival were compared between the groups. (3) Results: There were no differences regarding postoperative morbidity (iASS: 54% vs. cASS: 53% vs. no ASS: 64%, p = 0.448) and in-hospital mortality (iASS: 4% vs. cASS: 10% vs. no ASS: 3%, p = 0.198) between the groups. The overall survival (OS) and disease-free survival (DFS) did not differ in the groups when comparing the ASS-intake status (OS: iASS 17.8 months vs. cASS 19.6 months vs. no ASS 21.6 months, p = 0.489; DFS: iASS 14.0 months vs. cASS 18.3 months vs. no ASS 14.7 months, p = 0.957). Multivariate analysis revealed that age (hazard ratio (HR) 2.2, p < 0.001), lymph node-positive status (HR 2.0, p < 0.001), R status 1 or 2 (HR 2.8, p < 0.001) and differentiation with a grading of 3 (HR 1.7, p = 0.005) were significant independent prognostic factors regarding the OS. Moreover, age (HR 1.5, p = 0.040), lymph node-positive status (HR 1.8, p = 0.002) and high-grade (G3) carcinomas (HR 1.5, p = 0.037) could be identified as independent prognostic parameters for DFS. (4) Conclusions: In patients undergoing primary surgery for curative resection of pancreatic carcinoma, the perioperative intake of ASS had no significant impact on postoperative outcome, overall and disease-free survival.
CRIS-Team Scopus Importer:2023-06-09
Keywords: aspirin intake; disease-free survival; overall survival; pancreatic ductal adenocarcinoma; pancreatic resection

Impact of Patient Age on Postoperative Short-Term and Long-Term Outcome after Pancreatic Resection of Pancreatic Ductal Adenocarcinoma - Hackner, Danilo; Hobbs, Mirianna; Merkel, Susanne; Siepmann, Timo; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Cancers, 2022)
Simple Summary Pancreatic ductal adenocarcinoma (PDAC) is frequently seen in elderly patients. The aim of our retrospective study was to evaluate the impact of age on postoperative short-term and long-term outcomes in patients undergoing curative pancreatic resection for PDAC. Our data confirm that pancreatic resections can be performed with equal short-term outcomes even in older age. However, patient age significantly influenced the overall and disease-free survival of patients with PDAC undergoing primary resection in curative intent. Therefore, the choice of the optimal therapy concept for each patient should be individualized taking into account the patient's age. (1) Purpose: to evaluate the impact of age on postoperative short-term and long-term outcomes in patients undergoing curative pancreatic resection for PDAC. (2) Methods: This retrospective single-center study comprised 213 patients who had undergone primary resection of PDAC from January 2000 to December 2018 at the University Hospital of Erlangen, Germany. Patients were stratified according the age into two groups: younger (<= 70 years) and older (>70 years) patients. Postoperative outcome and long-term survival were compared between the groups. (3) Results: There were no significant differences regarding inhospital morbidity (58% vs. 67%, p = 0.255) or inhospital mortality (2% vs. 7%, p = 0.073) between the two groups. The median overall survival (OS) and disease-free survival (DFS) were significantly shorter in elderly patients (OS: 29.2 vs. 17.1 months, p < 0.001, respectively; DFS: 14.9 vs. 10.4 months, p = 0.034). Multivariate analysis revealed that age was a significant independent prognostic predictor for OS and DFS (HR 2.23, 95% CI 1.58-3.15; p < 0.001 for OS and HR 1.62, 95% CI 1.17-2.24; p = 0.004 for DFS). (4) Conclusion: patient age significantly influenced overall and disease-free survival in patients with PDAC undergoing primary resection in curative intent.
CRIS-Team WoS Importer:2022-09-09

Impact of Structured Postoperative Surveillance on Survival in Patients with Resected Pancreatic Adenocarcinoma - Jacobsen, Anne; Flessa, Maarten; Abels, Anna-Lena; Czubayko, Franziska; Mittelstädt, Anke; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Cancers, 2025)
Background: This study aimed to investigate whether structured surveillance after resection of PDAC has an impact on survival. Methods: 206 patients who underwent PDAC resection at the University Hospital Erlangen between 2005 and 2020 and survived for at least 90 days postoperatively were included in this retrospective study. The impact of surveillance (structured vs. no structured surveillance) respectively of recurrence patterns (recurrence in follow-up vs. symptomatic recurrence) on overall and disease-free survival was investigated. Results: A total of 157 patients (76%) participated in a structured surveillance program after pancreatic resection. During a mean follow-up of 28.5 months, 137 patients (67%) developed recurrence. Patients with structured surveillance showed significantly better outcomes for overall survival after surgery (OSaS: 29.2 months with structured surveillance vs. 16.4 months without, p < 0.001), overall survival after recurrence (OSaR: 10.8 months vs. 3.6 months, p < 0.001), and disease-free survival (DFS: 14.8 months vs. 11.4 months, p = 0.010). In a subgroup analysis of 112 patients with recurrence, survival benefits were observed for those whose recurrence was detected during follow-up compared to those with symptomatic recurrence (OSaS: 24.8 months in the follow-up group vs. 17.2 months in the symptomatic group, p < 0.001; OSaR: 12.6 months vs. 6.5 months, p < 0.001). Conclusion: This study provides evidence that structured surveillance after PDAC resection is beneficial for both overall and disease-free survival. However, randomized studies are needed to confirm the positive impact of structured surveillance programs on survival after pancreatic resection.
CRIS-Team Scopus Importer:2025-05-23
Keywords: follow-up; pancreatic cancer; pancreatic ductal adenocarcinoma; recurrence; surveillance

Influence of body mass index on long-term outcome in patients with rectal cancer-a single centre experience - Kalb, Maximilian; Langheinrich, Melanie C.; Merkel, Susanne; Krautz, Christian; Brunner, Maximilian; Bénard, Alan; Weber, Klaus; Pilarsky, Christian; Grützmann, Robert; Weber, Georg (Cancers, 2019)
Background: Excess bodyweight is known to influence the risk of colorectal cancer; however, little evidence exists for the influence of the body mass index (BMI) on the long-term outcome of patients with rectal cancer. Methods: We assessed the impact of the BMI on the risk of local recurrence, distant metastasis and overall-survival in 612 patients between 2003 and 2010 after rectal cancer diagnosis and treatment at the University Hospital Erlangen. A Cox-regression model was used to estimate the hazard ratio and multivariate risk of mortality and distant-metastasis. Median follow up-time was 58 months. Results: Patients with obesity class II or higher (BMI ≥ 35 kg/m2, n = 25) and patients with underweight (BMI < 18.5 kg/m2, n = 5) had reduced overall survival (hazard ratio (HR) = 1.6; 95% confidence interval (CI) 0.9-2.7) as well as higher rates of distant metastases (hazard ratio HR = 1.7; 95% CI 0.9-3.3) as compared to patients with normal bodyweight (18.5 ≤ BMI < 25 kg/m2, n = 209), overweight (25 ≤ BMI <30 kg/m2, n = 257) or obesity class I (30 ≤ BMI >35 kg/m2, n = 102). There were no significant differences for local recurrence. Conclusions: Underweight and excess bodyweight are associated with lower overall survival and higher rates of distant metastasis in patients with rectal cancer.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Body mass index; Distant metastasis; Overall survival; Rectal cancer

Influence of Hospital Volume Effects and Minimum Caseload Requirements on Quality of Care in Pancreatic Surgery in Germany - Krautz, Christian; Denz, Axel; Grützmann, Robert; Weber, Georg (Visceral Medicine, 2017)
Numerous international studies have identified hospital volume as significant independent variable of death following pancreatic surgery. Most of these studies were limited to regions of countries or portions of a national population and did not include data on volume-outcome effects in Germany.The Medline database was systematically searched to identify studies that analyzed volume-outcome relationships and effects of minimum caseload requirements on outcomes of pancreatic surgery in Germany.Recent observational studies utilizing German hospital discharge data confirmed that patients undergoing pancreatic surgery in Germany also have better outcomes when treated in facilities with high annual caseloads. Besides a decreased risk of in-hospital mortality, there is also a reduced risk of 1-year mortality in high-volume hospitals. In addition, there is evidence that adherence to already existing minimum caseload requirements reduces morbidity and mortality of pancreatic surgery in Germany. As a result of an insufficient centralization in the recent past, however, a large proportion of hospitals that perform pancreatic surgery still do not meet minimum caseload requirements.Specific measures (i.e. sanctions for failure to achieve minimum volumes) that initiate a sufficient centralization process without threatening patient access to surgical care are needed.
EVALuna2:15293

Influence of interrupted versus continuous suture technique on intestinal anastomotic leakage rate in patients with Crohn’s disease — a propensity score matched analysis - Mittelstädt, Anke; von Löffelholz, Tobias; Weber, Klaus; Denz, Axel; Krautz, Christian; Grützmann, Robert; Weber, Georg; Brunner, Maximilian (International Journal of Colorectal Disease, 2022)
Purpose: Intestinal anastomosis is a crucial step in most intestinal resections, as anastomotic leakage is often associated with severe consequences for affected patients. There are especially two different techniques for hand-sewn intestinal anastomosis: the interrupted suture technique (IST) and the continuous suture technique (CST). This study investigated whether one of these two suture techniques is associated with a lower rate of anastomotic leakage. Methods: A retrospective review of 332 patients with Crohn’s disease who received at least one hand-sewn colonic anastomosis at our institution from 2010 to 2020 was performed. Using propensity score matching 183 patients with IST were compared to 96 patients with CST in regard to the impact of the anastomotic technique on patient outcomes. Results: Overall anastomotic leakage rate was 5%. Leakage rate did not differ between the suture technique groups (IST: 6% vs. CST: 3%, p = 0.393). Multivariate analysis revealed the ASA score as only independent risk factor for anastomotic leakage (OR 5.3 (95% CI = 1.2–23.2), p = 0.026). Suture technique also showed no significant influence on morbidity and the re-surgery rate in multivariate analysis. Conclusion: Our data suggest that the chosen suture technique (interrupted vs. continuous) has no influence on postoperative outcome, especially on anastomotic leakage rate. This finding should be confirmed by a randomized controlled trial.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Anastomotic leakage; Continuous suture technique; Crohn’s disease; Interrupted suture technique; Intestinal anastomosis

In-hospital mortality and failure to rescue following hepatobiliary surgery in Germany - a nationwide analysis - Krautz, Christian; Gall, Christine; Gefeller, Olaf; Nimptsch, Ulrike; Mansky, Thomas; Brunner, Maximilian; Grützmann, Robert; Kersting, Stephan; Weber, Georg (BMC Surgery, 2020)
BACKGROUND: Recent observational studies on volume-outcome associations in hepatobiliary surgery were not designed to account for the varying extent of hepatobiliary resections and the consequential risk of perioperative morbidity and mortality. Therefore, this study aimed to determine the risk-adjusted in-hospital mortality for minor and major hepatobiliary resections at the national level in Germany and to examine the effect of hospital volume on in-hospital mortality, and failure to rescue. METHODS: All inpatient cases of hepatobiliary surgery (n = 31,114) in Germany from 2009 to 2015 were studied using national hospital discharge data. After ranking hospitals according to increasing hospital volumes, five volume categories were established based on all hepatobiliary resections. The association between hospital volume and in-hospital mortality following minor and major hepatobiliary resections was evaluated by multivariable regression methods. RESULTS: Minor hepatobiliary resections were associated with an overall mortality rate of 3.9% and showed no significant volume-outcome associations. In contrast, overall mortality rate of major hepatobiliary resections was 10.3%. In this cohort, risk-adjusted in-hospital mortality following major resections varied widely across hospital volume categories, from 11.4% (95% CI 10.4-12.5) in very low volume hospitals to 7.4% (95% CI 6.6-8.2) in very high volume hospitals (risk-adjusted OR 0.59, 95% CI 0.41-0.54). Moreover, rates of failure to rescue decreased from 29.38% (95% CI 26.7-32.2) in very low volume hospitals to 21.38% (95% CI 19.2-23.8) in very high volume hospitals. CONCLUSIONS: In Germany, patients who are undergoing major hepatobiliary resections have improved outcomes, if they are admitted to higher volume hospitals. However, such associations are not evident following minor hepatobiliary resections. Following major hepatobiliary resections, 70-80% of the excess mortality in very low volume hospitals was estimated to be attributable to failure to rescue.
CRIS-Team Scopus Importer:2020-08-07

Integrated Biosensor for Rapid and Point-of-Care Sepsis Diagnosis - Min, Jouha; Nothing, Maria Grazia; Coble, Ben; Zheng, Hui; Park, Jongmin; Im, Hyungsoon; Castro, Cesar M.; Swirski, Filip K.; Weissleder, Ralph; Lee, Hakho; Weber, Georg (ACS nano, 2018)
Sepsis is an often fatal condition that arises when the immune response to an infection causes widespread systemic organ injury. A critical unmet need in combating sepsis is the lack of accurate early biomarkers that produce actionable results in busy clinical settings. Here, we report the development of a point-of-care platform for rapid sepsis detection. Termed IBS (integrated biosensor for sepsis), our approach leverages (i) the pathophysiological role of cytokine interleukin-3 (IL-3) in early sepsis and (ii) a hybrid magneto-electrochemical sensor for IL-3 detection. The developed platform produces test results within 1 h from native blood samples and detects IL-3 at a sensitivity of <10 pg/mL; this performance is >5-times faster and >10-times more sensitive than conventional enzyme-linked immunoadsorbent assays, the current gold standard. Using clinical samples, we show that elevated plasma IL-3 levels are associated with high organ failure rate and thus greater risk of mortality, confirming the potential of IL-3 as a sepsis diagnostic biomarker. With further system development ( e. g., full automation, data security measures) and rigorous validation studies, the compact and fast IBS could be a practical clinical tool for timely diagnosis and proactive treatment of sepsis.
EVALuna2:210713

Interleukin-3 amplifies acute inflammation and is a potential therapeutic target in sepsis - Chousterman, B. G.; He, S.; Fenn, A. M.; Nairz, M.; Anzai, A.; Brenner, T.; Uhle, F.; Iwamoto, Y.; Robbins, C. S.; Noiret, L.; Maier, S. L.; Znnchen, T.; et al. (2016)
EVALuna2:15268

Interleukin-3 is a predictive marker for severity and outcome during SARS-CoV-2 infections - Bénard, Alan; Jacobsen, Anne; Brunner, Maximilian; Krautz, Christian; Klösch, Bettina; Swierzy, Izabela; Naschberger, Elisabeth; Podolska, Malgorzata; Kouhestani, Dina; David, Paul; Birkholz, Torsten; Castellanos, Ixchel; et al. (Nature Communications, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a worldwide health threat. In a prospective multicentric study, we identify IL-3 as an independent prognostic marker for the outcome during SARS-CoV-2 infections. Specifically, low plasma IL-3 levels is associated with increased severity, viral load, and mortality during SARS-CoV-2 infections. Patients with severe COVID-19 exhibit also reduced circulating plasmacytoid dendritic cells (pDCs) and low plasma IFNα and IFNλ levels when compared to non-severe COVID-19 patients. In a mouse model of pulmonary HSV-1 infection, treatment with recombinant IL-3 reduces viral load and mortality. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating pDCs into the airways by stimulating CXCL12 secretion from pulmonary CD123+ epithelial cells, both, in mice and in COVID-19 negative patients exhibiting pulmonary diseases. This study identifies IL-3 as a predictive disease marker for SARS-CoV-2 infections and as a potential therapeutic target for pulmunory viral infections.
CRIS-Team Scopus Importer:2021-03-05

Interleukin-3 protects against secondary viral infections in sepsis - Benard, A.; Weber, Georg (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-05

Interleukin-3 protects against viral pneumonia in sepsis by enhancing plasmacytoid dendritic cell recruitment into the lungs and T cell priming - Benard, Alan; Hansen, Frederik; Uhle, Florian; Klösch, Bettina; Czubayko, Franziska; Mittelstädt, Anke; Jacobsen, Anne; David, Paul; Podolska, Malgorzata; Anthuber, Anna; Swierzy, Izabela; Schaack, Dominik; et al. (Frontiers in Immunology, 2023)
Rationale: Sepsis, a global health burden, is often complicated by viral infections leading to increased long-term morbidity and mortality. Interleukin-3 (IL-3) has been identified as an important mediator amplifying acute inflammation in sepsis; however, its function in the host response to viral infections during sepsis remains elusive. Objectives: To investigate the role of IL-3 during viral pneumonia in sepsis. Methods: We included septic patients from two different cohorts and used in vitro and in vivo assays. The obtained data were substantiated using a second model (SARS-CoV-2 infections). Measurements and main results: Low plasma IL-3 levels were associated with increased herpes simplex virus (HSV) airway infections in septic patients, resulting in reduced overall survival. Likewise, Il-3-deficient septic mice were more susceptible to pulmonary HSV-1 infection and exhibited higher pulmonary inflammation than control mice. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating plasmacytoid dendritic cells (pDCs) into the airways and by enhancing pDC-mediated T cell activation upon viral stimulation. Interestingly, the ability of IL-3 to improve adaptive immunity was confirmed in patients with SARS-CoV-2 infections. Conclusion: Our study identifies IL-3 as a predictive disease marker for viral reactivation in sepsis and reveals that IL-3 improves antiviral immunity by enhancing the recruitment and the function of pDCs.
CRIS-Team Scopus Importer:2023-03-24
Keywords: interleukin-3; plasmacytoid dendritic cells; sepsis; T cell priming; viral pneumonia

Intestinal graft-versus-host disease is driven by BATF-dependent IL-7R(hi)GM-CSF+ T cells - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Buettner-Herold, Maike; Kitowski, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (2018)
EVALuna2:207769

Laparoscopic Right Hemicolectomy with Complete Mesocolic Excision (CME) Laparoskopische Hemikolektomie rechts mit kompletter mesokolischer Exzision (CME) - Brunner, Maximilian; Wiesmüller, Felix; Weber, Klaus; Maak, Matthias; Kersting, Stephan; Grützmann, Robert; Krautz, Christian; Weber, Georg (Zentralblatt für Chirurgie, 2020)
CRIS-Team Scopus Importer:2020-03-17

Lehrfilm Facharztweiterbildung: Hemithyreoidektomie mit Neuromonitoring des N. laryngeus recurrens - Brunner, Maximilian; Bleichroth, Hannah; Linke, Katja; Krautz, Christian; Grützmann, Robert; Kersting, Stephan; Weber, Georg (Zentralblatt für Chirurgie, 2019)
INTRODUCTION: The mean prevalence of thyroid nodules in adults is about 20% and increases with age. Most of the thyroid nodules are benign, and are rarely malignant. However, malignancy can often only be conclusively determined after resection. Therefore, it is essential that the surgical technique should be free of complications. Despite all published minimally invasive techniques, the open procedure via a Kocher incision is still standard and commonly used in a teaching setting. This standardised technique is presented step-by-step in the video. INDICATION: Sonographic and MIBI-scintigraphic possibly malignant solitary node in the right thyroid lobe. PROCEDURE: Hemithyreoidectomy with neuromonitoring of recurrent laryngeal nerve. CONCLUSION: Hemithyroidectomy is an adequate primary therapy for a solitary possibly malignant thyroid nodule. Intraoperative neuromonitoring to identify and protect the recurrent laryngeal nerve, visualisation and protection of the parathyroid glands without compromising blood circulation and careful hemostasis are the main pillars of low risk surgery of the thyroid.
CRIS-Team Scopus Importer:2019-12-24

Management of Complications of Pancreatic Anastomoses - Schmid, Axel; Uder, Michael; Grützmann, Robert; Weber, Georg (Zentralblatt für Chirurgie, 2017)
Background The pancreatic anastomosis may be the Achilles heel in pancreatic surgery. When a postoperative pancreatic fistula develops, be it mild or severe, in some cases life-threatening, POPF-associated complications can occur. Objectives Possibilities for the prophylaxis, diagnosis and therapy of POPF and POPF-associated complications in an interdisciplinary setting. Results Differentiated diagnostic and therapeutic management of POPF grade A - C is supported by recent studies to reduce morbidity and mortality. Depending on time and severity of POPF and POPF-associated complications, a conservative/interventional or surgical approach is indicated. Conclusion With the precise classification of POPF and POPF-associated complications, interdisciplinary diagnostic and therapeutic management can reduce morbidity and mortality after pancreatic surgery.
EVALuna2:15303

Microbiome Patterns in Matched Bile, Duodenal, Pancreatic Tumor Tissue, Drainage, and Stool Samples: Association with Preoperative Stenting and Postoperative Pancreatic Fistula Development - Langheinrich, Melanie; Wirtz, Stefan; Kneis, Barbara; Gittler, Matthias M.; Tyc, Olaf; Schierwagen, Robert; Brunner, Maximilian; Krautz, Christian; Pilarsky, Christian; Trebicka, Jonel; Agaimy, Abbas; Grützmann, Robert; et al. (Journal of Clinical Medicine, 2020)
Postoperative complications after pancreatic surgery are still a significant problem in clinical practice. The aim of this study was to characterize and compare the microbiomes of different body compartments (bile duct, duodenal mucosa, pancreatic tumor lesion, postoperative drainage fluid, and stool samples; preoperative and postoperative) in patients undergoing pancreatic surgery for suspected pancreatic cancer, and their association with relevant clinical factors (stent placement, pancreatic fistula, and gland texture). For this, solid (duodenal mucosa, pancreatic tumor tissue, stool) and liquid (bile, drainage fluid) biopsy samples of 10 patients were analyzed using 16s rRNA gene next-generation sequencing. Our analysis revealed: (i) a distinct microbiome in the different compartments, (ii) markedly higher abundance of Enterococcus in patients undergoing preoperative stent placement in the common bile duct, (iii) significant differences in the beta diversity between patients who developed a postoperative pancreatic fistula (POPF B/C), (iv) patients with POPF B/C were more likely to have bacteria belonging to the genus Enterococcus, and (v) differences in microbiome composition with regard to the pancreatic gland texture. The structure of the microbiome is distinctive in different compartments, and can be associated with the development of a postoperative pancreatic fistula.
CRIS-Team WoS Importer:2020-11-06

Minimalinvasive Resektion zystischer Pankreasneoplasien - Brunner, Maximilian; Krautz, Christian; Grützmann, Robert; Weber, Georg (Zentralblatt für Chirurgie, 2023)
CRIS-Team Scopus Importer:2023-12-01
Keywords: Enukleation; minimalinvasive Pankreaschirurgie; Pankreasschwanzresektion; Pankreassegmentresektion; roboterassistierte Pankreaschirurgie; zystische Pankreasneoplasien

Nationwide In-hospital Mortality Following Pancreatic Surgery in Germany is Higher than Anticipated - Nimptsch, Ulrike; Krautz, Christian; Mansky, Thomas; Grützmann, Robert; Weber, Georg (Annals of Surgery, 2016)
We aimed to determine the unbiased mortality rates for pancreatic surgery procedures at the national level through a comprehensive analysis of every inpatient case in Germany.Several studies have proclaimed a general improvement of perioperative outcomes following pancreatic surgery. These results are challenged by recent analyses of large US databases that found strong volume-outcome relationships, with high mortality in low-volume facilities.All inpatient cases with a pancreatic surgery procedure code in Germany from 2009 to 2013 were identified from nationwide administrative hospital data. We determined the absolute number of patients and the in-hospital death rate for crucial subcategories such as medical indications and types of surgical procedure.A total of 58,003 inpatient episodes of pancreatic surgery were identified between 2009 and 2013. Annual case numbers increased significantly, which was primarily attributed to patients aged 70 years and older. The overall in-hospital mortality rate (10.1%) did not significantly change during the study period. Major pancreatic resections were associated with mortality ranging from 7.3% (distal pancreatectomy) to 22.9% (total pancreatectomy). Postoperative interventions indicative of severe complications were documented frequently (eg, more than 6 blood transfusions in 20% of all patients and relaparotomy in 16%). Their occurrence was associated with a dramatic increase in mortality.At the national level in Germany, perioperative mortality is higher than anticipated from previous studies. The absence of a significant reduction in overall mortality challenges current health policies that aim to improve the outcomes of high-risk surgical procedures in Germany.
EVALuna2:15249

Neue WSES-AAST-Leitlinie zum Trauma des Duodenums, des Pankreas und der extrahepatischen Gallengänge – Zusammenfassung und Kommentar - Hecker, A.; Hecker, M.; Riedel, J. G.; Hecker, B.; Doppstadt, C.; Weigand, M. A.; Coccolini, F.; Reichert, M.; Padberg, W.; Askevold, I.; Weber, Georg (Chirurg, 2020)
CRIS-Team Scopus Importer:2020-07-24

Neutrophil-to-Lymphocyte Ratio and Prognostic Nutritional Index Are Predictors for Overall Survival after Primary Pancreatic Resection of Pancreatic Ductal Adenocarcinoma: A Single Centre Evaluation - Hackner, Danilo; Merkel, Susanne; Weiß, Andreas; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Cancers, 2024)
Purpose: Prognostic inflammation-based parameters have been reported as useful tools in various oncologic diseases. Pancreatic ductal adenocarcinoma (PDAC) is characterized by a high mortality rate, making reliable prognostic markers highly desirable. However, there is still inconsistency in the literature regarding the efficacy of the different available scores. Methods: A total of 207 patients, who underwent primary resection of PDAC from January 2000 to December 2018 at the University Hospital of Erlangen, were included in this retrospective single-center study. Different biomarkers, including the preoperative neutrophil–lymphocyte ratio (NLR), the platelet–lymphocyte ratio (PLR), the c-reactive protein (CRP)–albumin ratio (CAR), the lymphocyte–CRP ratio (LCR), the prognostic nutritional index (PNI) and the modified Glasgow prognostic score (mGPS) were analyzed for their ability to predict overall survival (OS). Results: In our cohort, the median overall survival was 20.7 months. Among the investigated biomarkers, NLR and PNI were identified as independent prognostic markers (Hazard Ratio (HR) 1.6 (1.0–2.5), p = 0.048 and HR 0.6 (0.4–0.9), p = 0.018), whereas PLR, CAR, LCR and mGPS did not reach significance in the multivariate analysis. Subgroup analysis revealed that the prognostic value of NLR and PNI is particularly evident in locally advanced tumor stages (pT3/4 and pN+). Conclusions: The NLR and PNI could serve as valuable tools for estimating prognosis in patients with PDAC undergoing pancreatic resection in curative intention, especially in locally advanced tumor stages. However, conflicting results in the current literature highlight the need for further prospective studies to validate these findings.
CRIS-Team Scopus Importer:2024-09-06
Keywords: biomarkers; neutrophil-to-lymphocyte ratio; overall survival; pancreatic ductal adenocarcinoma; pancreatic resection; prognostic nutritional index

Ökonomische Auswirkung der COVID-19-Pandemie in der Allgemein- und Viszeralchirurgie: Ein Vergleich von Leistungs- und Erlösdaten zweier Kliniken aus Krankenhäusern unterschiedlicher Versorgungsstufen - Binder, Johannes; Brunner, Maximilian; Maak, Matthias; Denz, Axel; Grützmann, Robert; Krautz, Christian; Weber, Georg (Chirurg, 2021)
Background: During the first wave of the coronavirus disease 2019 (COVID-19) pandemic, German hospitals were required to limit the capacity for elective surgery to prevent the healthcare system from general overload. In March 2020, the German government passed the COVID-19 Hospital Relief Act that guaranteed compensation payments for these limitations. In this study the regional impact of this intervention were analyzed. Material and methods: The performance data and revenue figures for the departments of general and visceral surgery of the University Hospital of Erlangen (UKER) and the District Hospital St. Anna Höchstadt/Aisch (KKH) during the period from 1 April to 30 June 2019 were compared with the respective period in 2020. Results: There was a significant decrease in bed occupancy rates and case numbers of inpatient treatment. The latter declined by 20.06% in the UKER and 60.76% in the KKH. Nononcological elective surgery was reduced by 33.04% in the UKER and 60.87% in the KKH. The number of emergency procedures remained unchanged in the UKER, while they decreased by 51.58% in the KKH. The revenues from diagnosis-related groups (DRG) decreased by 22.12% (UKER) and 54% (KKH), respectively. After taking compensation payments and savings from variable material costs into account, the UKER recorded a loss of −3.87%, while there was a positive revenue effect of 6.5% in the KKH. Discussion: The nonselective restriction of elective surgery had a significant impact on patient care and revenue figures at both locations. With respect to the increase of intensive care capacities, such untargeted measures do not appear to be efficient. In addition, the fixed rate of compensation payments led to an unbalanced distribution of the financial aid between the two departments.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Coronavirus; DRG billing data; Hospital Relief Act; Surgery; Treatment quality

Omega suture technique for minimally invasive rectal anastomosis – a video vignette - Brunner, Maximilian; Weber, Klaus; Denz, Axel; Langheinrich, Melanie; Kersting, Stephan; Weber, Georg; Grützmann, Robert; Krautz, Christian (Colorectal Disease, 2023)
CRIS-Team Scopus Importer:2023-05-19

Oncological colorectal surgery during the COVID-19pandemic—a national survey - Brunner, Maximilian; Krautz, Christian; Kersting, Stephan; Stinner, Benno; Benz, Stefan R.; Grützmann, Robert; Weber, Georg (International Journal of Colorectal Disease, 2020)
Purpose: The aim of this study was to clarify the surgical supply situation of oncological colorectal patients in Germany during limitations of the OR caseload due to the COVID-19 pandemic. Methods: Between 11th and 19th April 2020, all members of a consortium of German colorectal cancer centers were invited to participate in a web-based survey on the current status of surgical care situation of colorectal cancer patients in Germany. Results: A total of 112 colorectal surgeons of 101 German hospitals participated in the survey. Eighty-seven percent of the participating hospitals had to reduce their total surgical caseload and 34% their surgical volume for oncological colorectal patients during COVID-19 pandemic. Restrictions of the surgical caseload were independent of the size of the hospital and the number of cases of COVID-19 in the federal state of the hospital. Sixteen percent of colorectal surgeons consider surgical limitations to be not justified and 78% to be justified only if the care of oncological patients is ensured. Ninety-five percent of the colorectal surgeons interviewed stated that all oncological colorectal patients with an indication for surgery should be operated in time, despite the current reservations for COVID-19 patients. For the majority of the respondents (63% and 51%, respectively), an extended waiting time for surgery of up to 2 weeks was acceptable for non-metastatic and metastatic patients, respectively. Conclusion: In Germany, there is a temporarily relevant reduction of surgical volume in oncological colorectal patients. Most colorectal surgeons stated that oncological colorectal surgery should not be compromised despite the measures taken during the COVID-19 pandemic.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Colorectal surgery; COVID-19 pandemic; Oncological surgery; SARS-CoV-2 infection; Surgical caseload

Palliative therapy concepts for pancreatic carcinoma - Brunner, Michaela; Grützmann, Robert; Weber, Georg (Chirurg, 2018)
The majority of patients with ductal pancreatic adenocarcinoma are already in a locally advanced or metastatic stage at the time of diagnosis and require palliative therapy. Interventional and operative measures are available for the restoration of biliary outflow in bile duct obstruction and the continuity of the upper intestinal lumen in duodenal or gastric outlet obstruction. In the presence of tumor-related pain, pain therapy according to the World Health Organization (WHO) scheme or a truncus coeliacus blockade, in cachexia a nutritional therapy and in thromboembolic events an anticoagulant therapy are used. An individualized palliative chemotherapy regimen should be selected for each patient, taking into account the patient's general condition and the side effects profile of the chemotherapeutic agents. Radiochemotherapy and local ablative therapies should currently only be used within the framework of studies. A palliative resection is not recommended according to current knowledge.
EVALuna2:212624

Pancreatoduodenectomy with or without prophylactic falciform ligament wrap around the hepatic artery for prevention of postpancreatectomy haemorrhage: randomized clinical trial (PANDA trial) - Welsch, Thilo; Muessle, Benjamin; Korn, Sandra; Sturm, Dorothee; Bork, Ulrich; Distler, Marius; Graehlert, Xina; Klimova, Anna; Trebesius, Nicole; Kleespies, Axel; Kees, Stefan; Beckert, Stefan; et al. (British Journal of Surgery, 2022)
Background: Postpancreatectomy haemorrhage (PPH) is a rare but potentially fatal complication after pancreatoduodenectomy. Preventive strategies are lacking with scarce data for support. The aim of this study was to investigate whether a prophylactic falciform ligament wrap around the hepatic and gastroduodenal artery can prevent PPH from these vessels.
CRIS-Team WoS Importer:2022-02-11

Pathogenic, immunologic, and clinical aspects of sepsis - update 2016 - Uhle, Florian; Chousterman, Benjamin G.; Grützmann, Robert; Brenner, Thorsten; Weber, Georg (Expert Review of Anti-Infective Therapy, 2016)
Sepsis is a major cause of death worldwide but its orchestrating components remain incompletely understood. On the one hand, development of sepsis results from an infectious focus that cannot be controlled by the immune system, but on the other, responding immune cells that can eliminate the infection inflict damage to the host by contributing to complications such as endothelial leakage, septic shock, and multiorgan failure.In this review we give a comprehensive overview of how sepsis occurs, which exogenous and endogenous factors might affect the immune-pathophysiological course of sepsis and finally how this knowledge translates into up-to-date definitions and therapeutic approaches. Expert commentary: Although new immunological mechanisms altering the course of sepsis have been identified recently, future research needs to address the limitations of experimental approaches, redirect the research focus into translational approaches, and finally evaluate personalized treatment strategies.
EVALuna2:15252

Plasma extracellular vesicle messenger RNA profiling identifies prognostic EV signature for non-invasive risk stratification for survival prediction of patients with pancreatic ductal adenocarcinoma - Han, Yi; Drobisch, Pascal; Krüger, Alexander; William, Doreen; Grützmann, Konrad; Böthig, Lukas; Polster, Heike; Seifert, Lena; Seifert, Adrian M.; Distler, Marius; Pecqueux, Mathieu; Riediger, Carina; et al. (Journal of Hematology & Oncology, 2023)
Background: The prognosis of pancreatic ductal adenocarcinoma (PDAC) is one of the most dismal of all cancers and the median survival of PDAC patients is only 6–8 months after diagnosis. While decades of research effort have been focused on early diagnosis and understanding of molecular mechanisms, few clinically useful markers have been universally applied. To improve the treatment and management of PDAC, it is equally relevant to identify prognostic factors for optimal therapeutic decision-making and patient survival. Compelling evidence have suggested the potential use of extracellular vesicles (EVs) as non-invasive biomarkers for PDAC. The aim of this study was thus to identify non-invasive plasma-based EV biomarkers for the prediction of PDAC patient survival after surgery. Methods: Plasma EVs were isolated from a total of 258 PDAC patients divided into three independent cohorts (discovery, training and validation). RNA sequencing was first employed to identify differentially-expressed EV mRNA candidates from the discovery cohort (n = 65) by DESeq2 tool. The candidates were tested in a training cohort (n = 91) by digital droplet polymerase chain reaction (ddPCR). Cox regression models and Kaplan–Meier analyses were used to build an EV signature which was subsequently validated on a multicenter cohort (n = 83) by ddPCR. Results: Transcriptomic profiling of plasma EVs revealed differentially-expressed mRNAs between long-term and short-term PDAC survivors, which led to 10 of the top-ranked candidate EV mRNAs being tested on an independent training cohort with ddPCR. The results of ddPCR enabled an establishment of a novel prognostic EV mRNA signature consisting of PPP1R12A, SCN7A and SGCD for risk stratification of PDAC patients. Based on the EV mRNA signature, PDAC patients with high risk displayed reduced overall survival (OS) rates compared to those with low risk in the training cohort (p = 0.014), which was successfully validated on another independent cohort (p = 0.024). Interestingly, the combination of our signature and tumour stage yielded a superior prognostic performance (p = 0.008) over the signature (p = 0.022) or tumour stage (p = 0.016) alone. It is noteworthy that the EV mRNA signature was demonstrated to be an independent unfavourable predictor for PDAC prognosis. Conclusion: This study provides a novel and non-invasive prognostic EV mRNA signature for risk stratification and survival prediction of PDAC patients.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Extracellular vesicles; mRNA biomarkers; Pancreatic ductal adenocarcinoma; Plasma extracellular vesicle; Prognosis

Pleural Resident Macrophages and Pleural IRA B Cells Promote Efficient Immunity Against Pneumonia by Inducing Early Pleural Space Inflammation - Benard, Alan; Podolska, Malgorzata; Czubayko, Franziska; Kutschick, Isabella; Klösch, Bettina; Jacobsen, Anne; Naschberger, Elisabeth; Brunner, Maximilian; Krautz, Christian; Trufa, Denis; Sirbu, Horia; Lang, Roland; et al. (Frontiers in Immunology, 2022)
Airway infection is a major cause of mortality worldwide. The identification of new mechanisms aiding in effective host immune response is therefore required. Here, we show that the specific depletion of the pleural immune cell compartment during bacterial pneumonia resulted in a reduced pulmonary immune response and increased mortality in mice. Bacterial airway infection provoked early pleural space (PS) inflammation characterized by innate response activator (IRA) B cell development and pleural large resident macrophage (LRM) necroptosis, the repopulation of LRMs being driven by cellular proliferation in situ. Necroptotic LRMs amplified PS inflammation by stimulating pleural Mincle-expressing macrophages whereas IRA B cells contributed partially to GM-CSF-induced PS inflammation. Upon pulmonary infection, the induction of PS inflammation resulted in reduced bacterial burden whereas the specific depletion of pleural resident macrophages led to increased mortality and bacterial burden and reduced pulmonary immunity. Moreover, mice in which B cells were unable to produce GM-CSF exhibited reduced CD103+ dendritic cells and reduced CD4+ T cell numbers in the draining lymph node. Altogether, our results describe a previously unrecognized mechanism of pleural space inflammation necessary for effective protection against bacterial airway infection.
CRIS-Team Scopus Importer:2022-05-13
Keywords: bacterial airway infection; IRA B cells; mincle; necroptosis; pleural resident macrophages; pleural space

Prognostic role of nutrition parameters on short- and long-term outcome in patients with primary resectable pancreatic ductal adenocarcinoma - Bareiß, Sophie; Merkel, Susanne; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Clinical Nutrition ESPEN, 2024)
Purpose: Nutrition status of patients with pancreatic ductal adenocarcinoma (PDAC) has gained an increasing importance - especially in the preoperative setting. The aim of the present study was to evaluate different preoperative nutritional parameters including body composition parameters regarding their impact on short- and long-term outcome in patients with resectable PDAC. Methods: This retrospective single center study included 162 patients, who underwent primary resection of PDAC from January 2003 to December 2018 at the University Hospital of Erlangen. The influence of different preoperative nutrition parameters as well as different CT-based body composition parameters on short- (major morbidity, postoperative pancreatic fistula (POPF) and longer hospital stay) as well as on long-term outcome (overall and disease-free survival) were tested using multiple regression analysis. Results: Major morbidity and POPF occurred in 30% respectively 18%. Median length of hospital stay was 18 days. Median overall and disease free survival were 20.3 respectively 12.0 months. Multivariate analysis revealed among the different nutritional parameters following independent predictors: PMTH (psoas muscle thickness/height) for major morbidity (HR 2.1, p = 0.038), PMA (psoas muscle area) for a prolonged hospital stay >18 days (HR 7.3, p = 0.010) and NRS (nutritional risk score) for overall survival (HR 1.7, p = 0.043). Conclusion: In our cohort, nutritional parameters played a minor role in predicting short- and long-term outcome in patients with primary resectable PDAC, as there were only significant associations between selected psoas muscle parameters and short-term outcome parameters and the nutritional risk score (NRS) with the overall survival.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Body composition; Nutrition; Outcome; Pancreatic ductal adenocarcinoma; Primary resection; Survival

Proposal of a Standardized Questionnaire to Structure Clinical Peer Reviews of Mortality and Failure of Rescue in Pancreatic Surgery - Brunner, Maximilian; Mücke, Franziska; Langheinrich, Melanie; Struller, Florian; Rueckert, Felix; Welsch, Thilo; Distler, Marius; Kersting, Stephan; Grützmann, Robert; Krautz, Christian; Weber, Georg (Journal of Clinical Medicine, 2021)
Background: Quality management tools such as clinical peer reviews facilitate root cause analysis and may, ultimately, help to reduce surgery-related morbidity and mortality. This study aimed to evaluate the reliability of a standardized questionnaire for clinical peer reviews in pancreatic surgery. Methods: All cases of in-hospital-mortality following pancreatic surgery at two high-volume centers (n = 86) were reviewed by two pancreatic surgeons. A standardized mortality review questionnaire was developed and applied to all cases. In a second step, 20 cases were randomly assigned to an online re-review that was completed by seven pancreatic surgeons. The overall consistency of the results between the peer review and online re-review was determined by Cohen's kappa (kappa). The inter-rater reliability of the online re-review was assessed by Fleiss' kappa (kappa). Results: The clinical peer review showed that 80% of the patient mortality was related to surgery. Post-operative pancreatic fistula (POPF) (36%) followed by post-pancreatectomy hemorrhage (PPH) (22%) were the most common surgical underlying (index) complications leading to in-hospital mortality. Most of the index complications yielded in abdominal sepsis (62%); 60% of the cases exhibited potential of improvement, especially through timely diagnosis and therapy (42%). There was a moderate to substantial strength of agreement between the peer review and the online re-review in regard to the category of death (surgical vs. non-surgical; kappa = 0.886), type of surgical index complication (kappa = 0.714) as well as surgical and non-surgical index complications (kappa = 0.492 and kappa = 0.793). Fleiss' kappa showed a moderate to substantial inter-rater agreement of the online re-review in terms of category of death (kappa = 0.724), category of common surgical index complications (kappa = 0.455) and surgical index complication (kappa = 0.424). Conclusion: The proposed questionnaire to structure clinical peer reviews is a reliable tool for root cause analyses of in-hospital mortality and may help to identify specific options to improve outcomes in pancreatic surgery. However, the reliability of the peer feedback decreases with an increasing specificity of the review questions.
CRIS-Team WoS Importer:2021-05-28

Pylorus-Preserving Pancreaticoduodenectomy (PPPD) with Segmental Portal Vein Resection - Brunner, Maximilian; Krautz, Christian; Maak, Matthias; Weber, Georg; Grützmann, Robert (Zentralblatt für Chirurgie, 2021)
CRIS-Team WoS Importer:2021-08-06

R1 resection for pancreatic carcinoma - Kersting, S.; Haller, F.; Grützmann, Robert; Weber, Georg (Chirurg, 2017)
Surgery is the only potentially curative therapeutic approach in patients with pancreatic ductal adenocarcinoma (PDAC); however, achieving a negative (R0) resection margin is not always possible.The impact of R1 resection margins on survival rates and treatment options (surgical and multimodal) for intraoperatively and postoperatively identified R1 resection margins.For intraoperatively diagnosed R1 resection margins, a re-resection (e.g. pancreas, main bile duct, stomach, superior mesenteric and portal vein) can be performed to achieve R0 resection margins. Arterial resections and the resection of additional organs are occasionally technically feasible and can be performed in an individual approach. New neoadjuvant and adjuvant treatment strategies have increased the rate of resectable PDAC and have improved the outcome of patients with R0/R1 resected PDACs.An R0 resection is the primary goal of surgery in patients with PDAC as R1 resections are correlated with a poor outcome.
EVALuna2:6902

Recurrence pattern and its risk factors in patients with resected pancreatic ductal adenocarcinoma – A retrospective analysis of 272 patients - Brunner, Maximilian; Flessa, Maarten; Jacobsen, Anne; Merkel, Susanne; Krautz, Christian; Weber, Georg; Grützmann, Robert (Pancreatology, 2024)
Background: The aim of this study was to investigate the patterns of recurrence and their associated risk factors in patients who underwent resection for pancreatic carcinoma. Methods: This retrospective study included 272 patients, who underwent Ro/R1-resection of PDAC from 2005 to 2020 at the University Hospital Erlangen. Risk factors for different recurrence patterns and the prognostic value of recurrence pattern on the overall survival after recurrence were evaluated. Results: 61 % of the patients experienced recurrence, mostly within the first 12 postoperative months (62 %) and in the form of metastases (87 %). The median overall survival from recurrence was 9.2 months. The preoperative absence of diabetes and the presence of lymph node metastasis were independent risk factors for recurrence and a preoperative CA19-9 exceeding 97 U/ml for early recurrence. Additionally, lymph node metastases were associated with a higher risk of metastatic recurrence. Early recurrence, but not the site of recurrence, was identified as an independent prognostic factor for worse overall survival from recurrence. Conclusion: The occurrence of recurrence and especially of early and metastatic recurrence are associated with a worse overall survival. Patients lacking preoperative diabetes, having high preoperative CA19-9 values and lymph node metastases are particularly at risk for (early) recurrence.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Early recurrence; Locoregional recurrence; Overall survival; Pancreatic ductal adenocarcinoma; Recurrence; Resection; Surgery

Reduced circulating B cells and plasma IgM levels are associated with decreased survival in sepsis - A meta-analysis - Krautz, Christian; Maier, Sarah L.; Brunner, Maximilian; Langheinrich, Melanie; Giamarellos-Bourboulis, Evangelos J.; Gogos, Charalambos; Armaganidis, Apostolos; Kunath, Frank; Grützmann, Robert; Weber, Georg (Journal of Critical Care, 2018)
BACKGROUND: B cell function and antibody production are crucial factors in host protection during inflammation. We aimed to synthesize the available evidence on the association between the reduction of circulating B cells and plasma immunoglobulin (IgM) levels and decreased survival during sepsis. METHODS: We performed a systematic search in PubMed, Embase, ISI Web of Knowledge, Cochrane Central Register of Controlled Trials, BioMed Central, and Science Direct. We selected studies with data on circulating B cells and plasma IgM levels within the initial 24 h after sepsis onset. RESULTS: In total nine studies (n = 992 patients) were identified. Circulating B cells were reduced in septic patients as compared to non-septic patients (mean difference [MD] -88.2 cells/μl; 95% confidence interval [CI] -148.6–27.9). Sepsis non-survivors showed a significant reduction of circulating B cells and IgM levels compared to sepsis survivors (MD -77.1 cells/μl; 95% CI -111.4–42.7 and MD -20.9 mg/dl; 95% CI -33.8–8.0, respectively). CONCLUSIONS: Our results suggest that a reduction of circulating B cells and IgM levels at sepsis onset are associated with decreased sepsis survival. However, due to methodological limitations and the risk of bias, we need further prospective studies to confirm this association. REGISTRATION: The protocol was registered (PROSPERO 2016:CRD42016053184).
EVALuna2:32856

Risk factors for appendiceal neoplasm and malignancy among patients with acute appendicitis - Brunner, Maximilian; Lapins, Philipp; Langheinrich, Melanie; Baecker, Justus; Krautz, Christian; Kersting, Stephan; Grützmann, Robert; Maak, Matthias; Weber, Georg (International Journal of Colorectal Disease, 2019)
Purpose: Non-operative management of acute uncomplicated appendicitis has shown promising results but might carry the risk of delayed diagnosis of premalignant or malignant appendiceal tumors found by chance in 0.7–2.5% of appendiceal specimen after appendectomy. Purpose of this study was to analyze whether appendiceal tumors are associated with a complicated appendicitis and to determine risk factors for appendiceal neoplasm and malignancy in patients with acute appendicitis. Methods: We performed a retrospective analysis of 1033 adult patients, who underwent appendectomy for acute appendicitis from 2010 to 2016 at the University hospital Erlangen. Data included patients’ demographics; comorbidities; pre-, intra- and postoperative findings; and histopathological results. Complicated appendicitis was defined in the presence of perforation or abscess. Results: Appendiceal neoplasm respectively malignancy rate was 2.8% respectively 1.5%. Using univariate analysis, we identified seven risk factors at least for appendiceal neoplasm or malignancy: age, ASA, C-reactive protein, appendiceal diameter, perforation, intraoperative perithyphilitic abscess, and complicated appendicitis. Risk for appendiceal neoplasm or malignancy was 4.4% respectively 2.7% in complicated acute appendicitis compared to 2.0% respectively 1.0% in uncomplicated appendicitis (p = 0.043 respectively p = 0.060). In multivariate analysis, age ≥ 50 years and a diameter of the appendix in the sonography ≥ 13 mm were independent risk factors predicting the presence of appendiceal neoplasm and malignancy. Conclusion: Among patients with appendicitis, there are relevant risk factors predicting appendiceal tumors, especially age and appendiceal diameter in sonography. But the identified risk factors have a low sensitivity and specificity, so obtaining a confident preoperative diagnosis is challenging.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Appendectomy; Appendiceal neoplasm; Complicated appendicitis; Malignancy; Risk factors

Risk Factors for Conversion from Laparoscopic to Open Appendectomy - Bancke Laverde, Bruno Leonardo; Maak, Matthias; Langheinrich, Melanie; Kersting, Stephan; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Journal of Clinical Medicine, 2023)
(1) Background: Since its introduction in the 1990s, laparoscopic appendectomy has become established over the years and is today considered the standard therapy for acute appendicitis. In some cases, however, a conversion to the open approach is still necessary. The primary aim of this study was to identify risk factors for the need to convert from the laparoscopic to an open approach during appendectomy for acute appendicitis. (2) Methods: A retrospective analysis of 1220 adult patients who underwent laparoscopic appendectomy for acute appendicitis from 2010 to 2020 at the University Hospital Erlangen was performed. Data, including patient demographics and pre-, intra-, and postoperative findings, were collected and compared between patients with and without conversion. (3) Results: The conversion rate in our cohort was 5.5%. A higher preoperative WBC count and CRP (OR 1.9, p = 0.042, and OR 2.3, p = 0.019, respectively), as well as the presence of intraoperative perforation, necrosis or gangrene, perityphlitic abscess and peritonitis (OR 3.2, p = 0.001; OR 2.3, p = 0.023; OR 2.6, p = 0.006 and OR 2.0, p = 0.025, respectively) were identified as independent risk factors for conversion from the laparoscopic to the open approach. Conversion was again independently associated with higher morbidity (OR 2.2, p = 0.043). (4) Conclusion: The laparoscopic approach is feasible and safe in the majority of patients with acute appendicitis. Only increased inflammatory blood markers could be detected as the preoperative risk factors potentially influencing the choice of surgical approach but only with low specificity and sensitivity. For the decision to convert, intraoperative findings are additionally crucial. However, patients with conversion should receive special attention in the postoperative course, as these have an increased risk of developing complications.
CRIS-Team Scopus Importer:2023-07-28
Keywords: acute appendicitis; conversion; laparoscopic approach; morbidity

Risk Factors for Postoperative Major Morbidity, Anastomotic Leakage, Re-Surgery and Mortality in Patients with Colonic Perforation. - Brunner, Maximilian; Gärtner, Lara; Weiß, Andreas; Weber, Klaus; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert (Journal of Clinical Medicine, 2024)
Background/Objectives: This study aimed to determine the risk factors associated with postoperative major morbidity, anastomotic/suture leakage, re-surgery and mortality in patients undergoing emergency surgery for colonic perforation. Methods: A total of 204 adult patients treated surgically for colonic perforation from 2016 to 2021 at the University Hospital Erlangen were included in a retrospective analysis. Patient demographics and pre-, intra- and postoperative parameters were obtained and evaluated among various outcome groups (in-hospital major morbidity, anastomotic/suture leakage, re-surgery and 90-day mortality). Results: Postoperative in-hospital major morbidity, anastomotic/suture leakage, need of re-surgery and 90-day mortality occurred in 45%, 12%, 25% and 12% of the included patients, respectively. Independent risk factors for in-hospital major morbidity were identified and included the presence of any comorbidity, a significantly reduced preoperative general condition, the localization of perforation in the right hemicolon and the need for an intraoperative blood transfusion. The only independent risk factor for anastomotic/suture leakage was the presence of any comorbidity, whereas no independent risk factors for re-surgery were found. An age > 65 years, a significantly reduced preoperative general condition and the need for an intraoperative blood transfusion were independent risk factors for 90-day mortality. Conclusions: Our study identified risk factors impacting postoperative outcomes in patients undergoing emergency surgery for colonic perforation. These patients should receive enhanced postoperative care and may benefit from individualized and targeted therapeutic approaches.
EVALuna2:582568

Risk factors for postoperative morbidity, prolonged length of stay and hospital readmission after appendectomy for acute appendicitis - Laverde, Bruno Leonardo Bancke; Maak, Matthias; Langheinrich, Melanie; Kersting, Stephan; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (European Journal of Trauma and Emergency Surgery, 2023)
PurposeThe aim of the present study was to identify risk factors associated with postoperative morbidity and major morbidity, with a prolonged length of hospital stay and with the need of readmission in patients undergoing appendectomy due to acute appendicitis.MethodsWe performed a retrospective analysis of 1638 adult patients who underwent emergency appendectomy for preoperatively suspected acute appendicitis from 2010 to 2020 at the University Hospital Erlangen. Data including patient demographics, pre-, intra-, and postoperative findings were collected and compared between different outcome groups (morbidity, major morbidity, prolonged length of postoperative hospital stay (LOS) and readmission) from those patients with verified acute appendicitis (n = 1570).ResultsRate of negative appendectomies was 4%. In patients with verified acute appendicitis, morbidity, major morbidity and readmission occurred in 6%, 3% and 2%, respectively. Mean LOS was 3.9 days. Independent risk factors for morbidity were higher age, higher preoperative WBC-count and CRP, lower preoperative hemoglobin, longer time to surgery and longer duration of surgery. As independent risk factors for major morbidity could be identified higher age, higher preoperative CRP, lower preoperative hemoglobin and longer time to surgery. Eight parameters were independent risk factors for a prolonged LOS: higher age, higher preoperative WBC-count and CRP, lower preoperative hemoglobin, need for conversion, longer surgery duration, presence of intraoperative complicated appendicitis and of postoperative morbidity. Presence of malignancy and higher preoperative WBC-count were independent risk factors for readmission.ConclusionAmong patients undergoing appendectomy for acute appendicitis, there are relevant risk factors predicting postoperative complications, prolonged hospital stays and readmission. Patients with the presence of the identified risk factors should receive special attention in the postoperative course and may benefit from a more individualized therapy.
CRIS-Team WoS Importer:2023-03-03

Risk Factors for Postoperative Morbidity, Suture Insufficiency, Re-Surgery and Mortality in Patients with Gastroduodenal Perforation - Treuheit, Julia; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Journal of Clinical Medicine, 2023)
(1) Background: The aim of the present study was to identify risk factors associated with postoperative morbidity, suture/anastomotic insufficiency, re-surgery, and mortality in patients undergoing surgery for gastroduodenal perforation. (2) Methods: A retrospective analysis of 273 adult patients who received surgical treatment for gastroduodenal perforation from January 2006 to June 2021 at the University Hospital Erlangen was performed. The patient demographics and preoperative, intraoperative, and postoperative parameters were collected and compared among the different outcome groups (in-hospital morbidity, suture/anastomotic insufficiency, re-surgery, and 90-day mortality). (3) Results: In-hospital morbidity, suture/anastomotic insufficiency, need for re-surgery, and 90-day mortality occurred in 71%, 10%, 26%, and 25% of patients, respectively. The independent risk factors for morbidity were a significantly reduced general condition, a lower preoperative hemoglobin level, and a higher preoperative creatinine level. The independent risk factors for suture/anastomotic insufficiency could be identified as an intake of preoperative steroids and a perforation localization in the proximal stomach or duodenum. The four parameters were independent risk factors for the need for re-surgery: a significantly reduced general condition, a perforation localization in the proximal stomach, a higher preoperative creatinine level, and a higher preoperative CRP level. An age over 66 years and a higher preoperative CRP level were independent risk factors for 90-day mortality. (4) Conclusions: Our study could identify relevant risk factors for the postoperative outcome of patients undergoing surgical treatment for gastroduodenal perforation. Patients exhibiting the identified risk factors should receive heightened attention in the postoperative period and may potentially benefit from personalized and tailored therapy.
CRIS-Team Scopus Importer:2023-10-20
Keywords: gastroduodenal perforation; morbidity; mortality; re-surgery; risk factors; surgery; suture insufficiency

Roboterassistierte Pankreassegmentresektion - Weber, Georg; Krautz, Christian; Grützmann, Robert; Brunner, Maximilian (Zentralblatt für Chirurgie, 2025)
Central pancreatectomy is an excellent alternative to left pancreatectomy for symptomatic benign or premalignant lesions of the pancreatic body or tail. A key advantage of this technique lies in the preservation of pancreatic parenchyma, resulting in a lower rate of postoperative diabetes mellitus. However, this procedure requires more complex reconstruction, which in turn is associated with an increased risk of morbidity.Insulinoma in the pancreatic body.Robot-assisted central pancreatectomy with pancreaticojejunostomy using a modified Blumgart technique.Central pancreatectomy is a generally rare and challenging pancreatic procedure, but clearly plays a significant role in modern pancreatic surgery due to its functional advantages. When appropriate and technically feasible, central pancreatectomy should be preferred to the alternative of left pancreatectomy and whenever possible, performed minimally invasively.
EVALuna2:582564

Roboterassistierte viszeralchirurgische Eingriffe in Deutschland: Eine Analyse zum aktuellen Stand sowie zu Trends der letzten 5 Jahre anhand von StuDoQ|Robotik-Registerdaten - Brunner, Maximilian; Elgendy, Amr; Denz, Axel; Weber, Georg; Grützmann, Robert; Krautz, Christian (Die Chirurgie, 2023)
Robot-assisted systems have been increasingly used in general surgery for several years. Accordingly, the number of systems installed in Germany has also rapidly increased. While around 100 robot-assisted systems were used in German hospitals in 2018, this figure had already risen to more than 200 by 2022. The aim of this article is to present the current state of development and trends in robotic surgery in Germany. For this purpose, data from the StuDoQ|Robotics register were analyzed. Furthermore, a descriptive analysis of concomitant diagnosis-related groups (DRG) data was carried out via the Federal Statistical Office (Destatis), for a better assessment of the representativeness of the StuDoQ|Robotics register data. In both data sets, the annual number of robot-assisted visceral surgery procedures in Germany steadily increased. Compared to the DRG data, only 3.7% up to a maximum of 36.7% of all robot-assisted procedures performed were documented in the StuDoQ|Robotics register, depending on the type of procedure. Colorectal resections were the most frequent robot-assisted procedures (StuDoQ: 32.5% and 36.7% vs. DRG data: 24.2% and 29.7%) and had, for example, low mortality rates (StuDoQ: 1% and 1% vs. DRG data: 2.3% and 1.3%). Due to the low coverage rates of robot-assisted esophageal, gastric, pancreatic and liver interventions, no valid statements could be derived from the StuDoQ data for these areas. With the current coverage rates, the informative value of the StuDoQ|Robotics register is considerably limited for some types of intervention. In the future, measures should therefore be explored that lead to a significant increase in the coverage rates.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Hospital billing data; Robotic colorectal surgery; Robotic hepato-pancreato-biliary surgery; Robotic surgery of the upper gastrointestinal tract; StuDoQ register

Robotische Pankreatoduodenektomie: Variationen der Pankreasanastomose in modifizierter Blumgart-Technik - Seeger, Philipp; Distler, Marius; Thomaschewski, Michael; Zimmermann, Markus; Heumann, Asmus; Uzunoglu, Faik Güntac; Grützmann, Robert; Weber, Georg; Brunner, Maximilian; Kersting, Stephan; Hackert, Thilo; Keck, Tobias; et al. (Zentralblatt für Chirurgie, 2024)
Zusammenfassung Zielsetzung Die wichtigste Komplikation nach Pankreatoduodenektomie ist die klinisch relevante Pankreasfistel. Um die Rate an Komplikationen zu senken, ist eine routinierte und standardisierte Operationstechnik zur Anlage der Pankreatojejunostomie notwendig. Indikationen Die Pankreatoduodenektomie ist im multimodalen Setting der Goldstandard zur Behandlung des lokal begrenzten Pankreaskopfkarzinoms und weiterer Pathologien. Das robotische Verfahren bietet als innovatives minimalinvasives Verfahren Vorteile bez. Morbiditat und Ergonomie. Methode Nach der Resektionsphase folgt die Rekonstruktion beginnend mit der Pankreatojejunostomie. Die aktuell meistverbreitete robotische Technik ist die Anastomose nach Blumgart: Dabei wird eine au ss ere Naht transpankreatisch zwischen Jejunalwand und dem gesamten Pankreasparenchym in ventrodorsaler Ausrichtung angelegt, die Spannungs- und Scherkrafte verteilt. Die innere Naht wird durch eine Duct-to-Mucosa-Naht des Pankreasganges mit einer kleinen Jejujunostomie erreicht. In diesem Manuskript werden verschiedene Varianten dieser Rekonstruktion in robotischer Technik gezeigt. Schlussfolgerung Hinsichtlich der wissenschaftlichen Evidenz zeigt keine Anastomosenvariante einen Vorteil. Das Outcome ist abhangig von der Expertise des Operateurs, entsprechend sollte diejenige Anastomosentechnik angewendet werden, fur die am meisten Erfahrung verfugbar ist. Die in diesem Beitrag gezeigten Variationen sollen fur Anwender den Fokus auf wichtige Details legen sowie Tipps und Tricks zur Durchfuhrung geben.
EVALuna2:582588

Simultaneous gene silencing of KRAS and anti-apoptotic genes as a multitarget therapy - Werner, Kristin; Lademann, Franziska; Thepkaysone, May-Linn; Jahnke, Beatrix; Aust, Daniela; Kahlert, Christoph; Weitz, Juergen; Grützmann, Robert; Pilarsky, Christian; Pilarsky, Christian; Weber, Georg (Oncotarget, 2016)
Pancreatic cancer is one of the most lethal tumor types worldwide and an effective therapy is still elusive. Targeted therapy focused against a specific alteration is by definition unable to attack broad pathway signaling modification. Tumor heterogeneity will render targeted therapies ineffective based on the regrowth of cancer cell sub-clones. Therefore multimodal therapy strategies, targeting signaling pathways simultaneously should improve treatment.SiRNAs against KRAS and the apoptosis associated genes BCLXL, FLIP, MCL1L, SURVIVIN and XIAP were transfected into human and murine pancreatic cancer cell lines. Induction of apoptosis was measured by Caspase 3/7 activation, subG1 FACS analysis and PARP cleavage. The therapeutic approach was tested in a subcutaneous allograft model with a murine cancer cell line.By using siRNAs as a systematic approach to remodel signal transduction in pancreatic cancer the results showed increasing inhibition of proliferation and apoptosis induction in vitro and in vivo. Thus, siRNAs are suitable to model multimodal therapy against signaling pathways in pancreatic cancer. Improvements in in vivo delivery of siRNAs against a multitude of targets might therefore be a potential therapeutic approach.
EVALuna2:15258

Survival outcome following surgical versus non-surgical treatment of colorectal lung metastasis—a retrospective cohort study - Denz, Axel; Hahn, Veronika; Weber, Klaus; Weber, Georg; Grützmann, Robert; Krautz, Christian; Brunner, Maximilian (Langenbecks Archives of Surgery, 2024)
Purpose: The optimal management of colorectal lung metastases (CRLM) is still controversial. The aim of this study was to compare surgical and non-surgical treatment for CRLM regarding the prognostic outcome. Methods: This retrospective single-center cohort study included 418 patients, who were treated from January 2000 to December 2018 at a German University Hospital due to their colorectal carcinoma and had synchronous or metachronous lung metastases. Patients were stratified according the treatment of the CRLM into two groups: surgical resection of CRLM versus no surgical resection of CRLM. The survival from the time of diagnosis of lung metastasis was compared between the groups. Results: Two- and 5-year overall survival (OS) from the time of diagnosis of lung metastasis was 78.2% and 54.6%, respectively, in our cohort. Patients undergoing pulmonary metastasectomy showed a significantly better 2- and 5-year survival compared to patients with non-surgical treatment (2-year OS: 98.1% vs. 67.9%; 5-year OS: 81.2% vs. 28.8%; p < 0.001). Multivariate Cox regression revealed the surgical treatment (HR 4.51 (95% CI = 2.33–8.75, p < 0.001) and the absence of other metastases (HR 1.79 (95% CI = 1.05–3.04), p = 0.032) as independent prognostic factors in patients with CRLM. Conclusion: Our data suggest that patients with CRLM, who qualify for surgery, benefit from surgical treatment. Randomized controlled trials are needed to confirm our findings. Clinical trial registry number: The work has been retrospectively registrated at the German Clinical Trial Registry (DRKS00032938).
CRIS-Team Scopus Importer:2024-04-26
Keywords: Colorectal carcinoma; Lung metastases; Non-surgical treatment; Outcome; Overall survival; Surgical resection

The B-cell inhibitory receptor CD22 is a major factor in host resistance to Streptococcus pneumoniae infection - Fernandes, Vitor E.; Ercoli, Giuseppe; Bénard, Alan; Brandl, Carolin; Fahnenstiel, Hannah; Müller-Winkler, Jennifer; Denny, Paul; Nitschke, Lars; Andrew, Peter W.; Weber, Georg (PLoS Pathogens, 2020)
Streptococcus pneumoniae is a major human pathogen, causing pneumonia and sepsis. Genetic components strongly influence host responses to pneumococcal infections, but the responsible loci are unknown. We have previously identified a locus on mouse chromosome 7 from a susceptible mouse strain, CBA/Ca, to be crucial for pneumococcal infection. Here we identify a responsible gene, Cd22, which carries a point mutation in the CBA/Ca strain, leading to loss of CD22 on B cells. CBA/Ca mice and gene-targeted CD22-deficient mice on a C57BL/6 background are both similarly susceptible to pneumococcal infection, as shown by bacterial replication in the lungs, high bacteremia and early death. After bacterial infections, CD22-deficient mice had strongly reduced B cell populations in the lung, including GM-CSF producing, IgM secreting innate response activator B cells, which are crucial for protection. This study provides striking evidence that CD22 is crucial for protection during invasive pneumococcal disease.
CRIS-Team Scopus Importer:2020-05-15

The Effect of GPRC5a on the Proliferation, Migration Ability, Chemotherapy Resistance, and Phosphorylation of GSK-3β in Pancreatic Cancer - Liu, Bin; Yang, Hai; Pilarsky, Christian; Weber, Georg (International Journal of Molecular Sciences, 2018)
Pancreatic cancer (PaCa) is the fourth leading cause of cancer-related death, and personalized targeted cancer therapy is becoming a promising treatment strategy for PaCa. The central approach of targeted therapy is to find a targetable key and an effective targeting method. In this study, the importance of GPRC5a (the G-protein-coupled receptor family C, member 5, group A) was identified using data mining methods based on published datasets. After analysis of the basic expression of GPRC5a in normal pancreas tissue and various PaCa cell lines, gene editing of GPRC5a in the human PaCa cell line MIA PaCa-2 and the mouse PaCa cell line TB32047 was performed using CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated proteins 9) to investigate the influence of GPRC5a on the proliferation and migration of PaCa cells as well as its effects on chemotherapy drug resistance. The results showed that GPRC5a was upregulated in PaCa tissues and various PaCa cell lines. Knockout of GPRC5a reduced the proliferation and migration ability of PaCa cell lines and suppressed the chemotherapy drug resistance of gemcitabine, oxaliplatin, and fluorouracil in PaCa cells. The phosphorylation of GSK-3β (Glycogen synthase kinase-3β) was found to be upregulated in the MIA PaCa-2 and TB32047 cells after GPRC5a knockout. In conclusion, GPRC5a was upregulated in PaCa leading to an enhanced drug resistance in PaCa cells. These results provide for the first time a theoretical basis for the development of an improved PaCa targeted therapy.
EVALuna2:210711

The impact of surgical experience and frequency of practice on perioperative outcomes in pancreatic surgery - Krautz, Christian; Haase, Elisabeth; Elshafei, Moustafa; Saeger, Hans Detlev; Distler, Marius; Grützmann, Robert; Weber, Georg (BMC Surgery, 2019)
Objective: We aimed to determine the impact of surgical experience and frequency of practice on perioperative morbidity and mortality in pancreatic surgery. Methods: 1281 patients that underwent pancreatic resections from 1993 to 2013 were retrospectively analyzed using logistic regression models. All cases were stratified according to the surgeon's level of experience, which was based on the number of previously performed pancreatic resections and the extent of received supervision (novice: N < 20/intensive; intermediate: N = 21-90/decreasing; and experienced surgeon: N > 90/none). Additional stratification was based on the frequency of practice (sporadic: 3 resections > 6 weeks, frequent: 3 resections ≤6 weeks). Results: The novice and experienced categories were related to a decreased risk of postoperative pancreatic fistulas (odds ratio [OR] 0.46, 95% confidence interval [CI] 0.26-0.82 and 0.54, 95% CI 0.36-0.82) and in-hospital mortality (OR 0.45, 95% CI 0.17-1.16 and 0.42, 95% CI 0.21-0.83) compared to the intermediate category. Frequent practice was associated with a significantly lower risk of delayed gastric emptying (OR 0.56, 95% CI 0.38-0.83), postpancreatectomy hemorrhage (OR 0.64, 95% CI 0.42-0.98) and in-hospital mortality (OR 0.45, 95% CI 0.24-0.87). Conclusions: Our results emphasize the importance of supervision within a pancreatic surgery training program. In addition, our data underline the need of a sufficient patient caseload to ensure frequent practice.
CRIS-Team Scopus Importer:2019-08-27
Keywords: Frequency of practice; In-hospital mortality; Pancreatic surgery; Perioperative outcomes; Surgical experience; Volume-outcome relationship

The Intratumoral and Intestinal Microbiome in Pancreatic Cancer - Langheinrich, Melanie; Wirtz, Stefan; Grützmann, Robert; Kersting, Stephan; Weber, Georg (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

The Multifaceted Functionality of Plasmacytoid Dendritic Cells in Gastrointestinal Cancers: A Potential Therapeutic Target? - Hansen, Frederik; David, Paul; Weber, Georg (Cancers, 2024)
Gastrointestinal (GI) tumors pose a significant global health burden, necessitating the exploration of novel therapeutic approaches. Plasmacytoid dendritic cells (pDCs) play a crucial role in tumor immunity, exhibiting both anti-tumor and pro-tumor effects. This review aims to summarize the role of pDCs in different types of GI tumors and assess their potential as therapeutic targets. In gastric cancer, hepatocellular carcinoma, and intrahepatic cholangiocarcinoma, increased infiltration of pDCs was associated with a worse outcome, whereas in esophageal cancer, pancreatic cancer, and colorectal cancer, pDC infiltration improved the outcome. Initial animal studies of gastric cancer and hepatocellular carcinoma showed that pDCs could be a successful therapeutic target. In conclusion, pDCs play a multifaceted role in GI tumors, influencing both anti-tumor immunity and tumor progression. Further research is needed to optimize their clinical application and explore combinatorial approaches.
CRIS-Team Scopus Importer:2024-07-12
Keywords: cholangiocarcinoma; colorectal cancer; esophageal cancer; gastric cancer; hepatocellular carcinoma; pancreatic cancer; pDCs; plasmacytoid dendritic cells

The prognostic value of the number of harvested negative lymph nodes in patients treated by esophagectomy with or without neoadjuvant chemoradiation - Brunner, Maximilian; Merkel, Susanne; Krautz, Christian; Kersting, Stephan; Grützmann, Robert; Weber, Georg (Anticancer Research, 2020)
Background/Aim: The prognostic value of the number of harvested negative lymph nodes (NLNs) in patients with node-negative esophageal carcinoma treated by esophagectomy with or without neoadjuvant chemoradiation is unclear. Patients and Methods: A total of 136 patients who underwent oncological esophagectomy with two-field lymphadenectomy from 1995 to 2014 were analyzed regarding the prognostic impact of NLNs. 86 patients received primary surgery (group 1) and 50 patients had preoperative chemoradiation followed by surgery (group 2). Results: The 5-year overall survival (OS) was 61.1%. Median lymph node harvest was significantly higher in group 1 (39 vs. 34 in group 2, p=0.007). In group 1, patients with a higher number of negative lymph nodes (>40) had a better OS [57.6% vs. 78.9%, HR=0.5 (0.3-0.9), p=0.026], whereas there was no significant difference in group 2 using the same cutoff (47.6% vs. 66.7%, p=0.476). Conclusion: The number of NLNs is an independent prognostic factor for patients with esophageal carcinoma treated by primary esophagectomy, but not in patients after neoadjuvant chemoradiation.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Esophageal carcinoma; Lymphadenectomy; Neoadjuvant chemoradiation; Oncological esophagectomy; Prognosis; Survival

The role of intraoperative swab during appendectomy in patients with uncomplicated and complicated appendicitis - Bancke Laverde, Bruno Leonardo; Maak, Matthias; Langheinrich, Melanie; Kersting, Stephan; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (International Journal of Colorectal Disease, 2023)
Introduction: Bacteria play an important role not only in pathogenesis of appendicitis but also in the postoperative course of patients. However, the usefulness of an intraoperative swab during appendectomy is controversial. The primary aim of this study was to investigate the impact of intraoperative swab during appendectomy on the postoperative outcome in patients with uncomplicated and complicated appendicitis. Methods: A retrospective analysis was conducted on a consecutive series of 1570 adult patients who underwent appendectomy for acute appendicitis at the University Hospital Erlangen between 2010 and 2020. Data regarding the intraoperative swab were collected and analyzed for the entire cohort as well as for patients with uncomplicated and complicated appendicitis. Results: An intraoperative swab was taken in 29% of the cohort. The bacterial isolation rate in the obtained intraoperative swabs was 51%, with a significantly higher rate observed in patients with complicated appendicitis compared to those with uncomplicated appendicitis (79% vs. 35%, p < 0.001). The presence of a positive swab was significantly associated with worse postoperative outcomes, including higher morbidity, increased need for re-surgery, and longer hospital stay, when compared to patients without a swab or with a negative swab. A positive swab was an independent risk factor for postoperative morbidity (OR 9.9 (95% CI 1.2–81.9), p = 0.034) and the need for adjustment of postoperative antibiotic therapy (OR 8.8 (95% CI 1.1–72.5), p = 0.043). However, a positive swab resulted in postoperative antibiotic therapy adjustment in only 8% of the patients with bacterial isolation in the swab. Conclusion: The analysis of swab samples obtained during appendectomy for acute appendicitis can help identify patients at a higher risk of a worse postoperative outcome. However, the frequency of antibiotic regime changes based on the swab analysis is low.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Appendectomy; Bacterial isolation; Complicated appendicitis; Intraoperative swab; Uncomplicated appendicitis

The use of single-stapling techniques reduces anastomotic complications in minimal-invasive rectal surgery - Brunner, Maximilian; Zu'bi, Alaa; Weber, Klaus; Denz, Axel; Langheinrich, Melanie; Kersting, Stephan; Grützmann, Robert; Krautz, Christian; Weber, Georg (International Journal of Colorectal Disease, 2022)
Background Leakage of rectal anastomoses is one of the most important and feared complications in colorectal surgery. Apart from patient-specific risk factors, technical aspects may influence the occurrence of anastomotic complications. This study investigated whether using single-stapling techniques (SST) instead of the double-stapling technique (DST) for minimal-invasive rectal anastomosis is associated with a lower rate of anastomotic complications. Methods A retrospective review of 272 patients who received a minimally invasive stapled rectal anastomosis (3-16 cm from the anal verge) at our institution from 2015 to 2020 was performed. In 131 patients, rectal anastomosis was created by SST (SST group), while 141 patients received a rectal anastomosis with crossing stapler lines (DST group). The impact of the anastomotic technique on patient outcomes was determined by uni- and multivariate analyses. Results Overall anastomotic leakage rate was 6%. Patients with SST anastomoses had a lower leakage rate than patients with DST anastomoses (3% vs. 9% in the DST group, p = 0.045). The rate of anastomotic stenosis was lower in the SST group than in the DST group (1% vs. 6%, p = 0.037). Overall morbidity and mortality did not differ between the two groups. Multivariate analysis showed that single-stapling techniques significantly reduce the risk of anastomotic leakage (OR 3.5 [1.0-11.5], p = 0.043). Conclusion The use of SST for rectal anastomosis may help to reduce anastomotic complications. This finding should be confirmed by a randomized controlled trial.
CRIS-Team WoS Importer:2022-07-01

Time to Surgery Does Not Affect Overall or Disease-Free Survival of Patients with Primary Resectable PDAC - Jacobsen, Anne; Hobbs, Mirianna; Merkel, Susanne; Mittelstädt, Anke; Czubayko, Franziska; Krautz, Christian; Grützmann, Robert; Brunner, Maximilian; Weber, Georg (Journal of Clinical Medicine, 2022)
(1) Background: Delay in therapy for pancreatic ductal adenocarcinoma (PDAC) may contribute to a worse outcome. The aim of this study was to investigate the prognostic value of time from diagnosis to surgery in patients undergoing upfront surgery for primarily resectable pancreatic carcinoma. (2) Methods: This retrospective single-center study included 214 patients who underwent primary resection of PDAC from January 2000 to December 2018 at University Hospital Erlangen. Using a minimum p-value approach, patients were stratified according to time to surgery (TtS) into two groups: TtS <= 23 days and TtS > 23 days. Postoperative outcome and long-term survival were compared. (3) Results: Median TtS was 25 days. The best cut-off for TtS was determined as 23 days. There were no differences regarding postoperative outcome or overall survival (OS) and disease-free survival (DFS) (OS: 23.8 vs. 20.4 months, p = 0.210, respectively, and DFS: 15.8 vs. 13.6 months, p = 0.187). Multivariate analysis revealed age, lymph node metastasis, tumor differentiation and resection status as significant independent prognostic predictors for OS and DFS. (4) Conclusions: A delay of surgery > 23 days after first diagnosis does not affect overall or disease-free survival of patients with primary resectable PDAC. However, the psychological impact of a delay to patients waiting for surgery should not be underestimated.
CRIS-Team WoS Importer:2022-08-26

Transverse Incision for Pancreatoduodenectomy Reduces Wound Complications: A Single-Center Analysis of 399 Patients - Junker, Stefanie; Jacobsen, Anne; Merkel, Susanne; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Journal of Clinical Medicine, 2023)
Background: Even if the minimally invasive approach is advancing in pancreatic surgery, the open approach is still the standard for a pancreatoduodenectomy. There are two types of incisions used: the midline incision (MI) and transverse incision (TI). The aim of this study was to compare these two incision types, especially regarding wound complications. Methods: A retrospective review of 399 patients who underwent a pancreatoduodenectomy at the University Hospital Erlangen between 2012 and 2021 was performed. A total of 169 patients with MIs were compared with 230 patients with TIs, with a focus on postoperative fascial dehiscence, postoperative superficial surgical site infection (SSSI) and the occurrence of incisional hernias during follow-up. Results: Postoperative fascial dehiscence, postoperative SSSI and incisional hernias occurred in 3%, 8% and 5% of patients, respectively. Postoperative SSSI and incisional hernias were significantly less frequent in the TI group (SSI: 5% vs. 12%, p = 0.024; incisional hernia: 2% vs. 8%, p = 0.041). A multivariate analysis confirmed the TI type as an independent protective factor for the occurrence of SSSI and incisional hernias (HR 0.45 (95% CI = 0.20–0.99), p = 0.046 and HR 0.18 (95% CI = 0.04–0.92), p = 0.039, respectively). Conclusion: Our data suggest that the transverse incision for pancreatoduodenectomy is associated with reduced wound complications. This finding should be confirmed by a randomized controlled trial.
CRIS-Team Scopus Importer:2023-05-12
Keywords: fascial dehiscence; incisional hernia; midline incision; pancreatoduodenectomy; surgical site infection; transverse incision

Tumor Infiltration with CD20+CD73+ B Cells Correlates with Better Outcome in Colorectal Cancer - Hansen, Frederik; Wu, Zhiyuan; David, Paul; Mittelstädt, Anke; Jacobsen, Anne; Podolska, Malgorzata; Ubieta Hernández, Kenia; Brunner, Maximilian; Kouhestani, Dina; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; et al. (International Journal of Molecular Sciences, 2022)
Immunotherapy has become increasingly important in the treatment of colorectal cancer (CRC). Currently, CD73, also known as ecto-5′-nucleotidase (NT5E), has gained considerable interest as a potential therapeutic target. CD73 is one of the key enzymes catalyzing the conversion of extracellular ATP into adenosine, which in turn exerts potent immune suppressive effects. However, the role of CD73 expression on various cell types within the CRC tumor microenvironment remains unresolved. The expression of CD73 on various cell types has been described recently, but the role of CD73 on B-cells in CRC remains unclear. Therefore, we analyzed CD73 on B-cells, especially on tumor-infiltrating B-cells, in paired tumor and adjacent normal tissue samples from 62 eligible CRC patients. The highest expression of CD73 on tumor-infiltrating B-cells was identified on classswitched memory B-cells, followed by naive B-cells, whereas no CD73 expression was observed on plasmablasts. Clinicopathological correlation analysis revealed that higher CD73+ B-cells infiltration in the CRC tumors was associated with better overall survival. Moreover, metastasized patients showed a significantly decreased number of tumor-infiltrating CD73+ B-cells. Finally, neoadjuvant therapy correlated with reduced CD73+ B-cell numbers and CD73 expression on B-cells in the CRC tumors. As promising new immune therapies are being developed, the role of CD73+ B-cells and their subsets in the development of colorectal cancer should be further explored to find new therapeutic options.
CRIS-Team Scopus Importer:2022-05-20
Keywords: B-cells; CD20; CD73; colorectal cancer; neoadjuvant treatment

Tumor location determines tissue-specific recruitment of tumor-associated macrophages and antibody-dependent immunotherapy response - Lehmann, Birgit; Biburger, Markus; Brückner, Christin; Ipsen Escobedo, Andrea; Gordan, Sina; Lehmann, Christian; Vöhringer, David; Winkler, Thomas; Schaft, Niels; Dudziak, Diana; Sirbu, Horia; Nimmerjahn, Falk; et al. (Science immunology, 2017)
Despite recent advances in activating immune cells to target tumors, the presence of some immune cells, such as tumor-associated macrophages (TAMs) or tumor-associated neutrophils (TANs), may promote rather than inhibit tumor growth. However, it remains unclear how antibody-dependent tumor immunotherapies, such as cytotoxic or checkpoint control antibodies, affect different TAM or TAN populations, which abundantly express activating Fcγ receptors. In this study, we show that the tissue environment determines which cellular effector pathways are responsible for antibody-dependent tumor immunotherapy. Although TAMs derived from Ly6Chigh monocytes recruited by the CCL2-CCR2 axis were critical for tumor immunotherapy of skin tumors, the destruction of lung tumors was CCL2-independent and required the presence of colony-stimulating factor 2–dependent tissue-resident macrophages. Our findings suggest that TAMs may have a dual role not only in promoting tumor growth in certain tissue environments on the one hand but also in contributing to tumor cell destruction during antibody-mediated immunotherapy on the other hand.
EVALuna2:15237
Keywords: Cancer; Macrophages; Tumor associated macrophages; Antibodies; Tumor therapy; Immunotherapy

Upregulation of CD20 positive B-cells and B-cell aggregates in the tumor infiltration zone is associated with better survival of patients with pancreatic ductal adenocarcinoma - Brunner, Maximilian; Maier, Katharina; Rümmele, Petra; Jacobsen, Anne; Merkel, Susanne; Benard, Alan; Krautz, Christian; Kersting, Stephan; Grützmann, Robert; Weber, Georg (International Journal of Molecular Sciences, 2020)
Patients with pancreatic ductal adenocarcinoma (PDAC) normally have a poor long-term prognosis. However, some rare cases of long-term survivors have been reported. The tumor microenvironment, consisting of cellular and stromal components, possibly plays an important role and might influence prognosis. In this context, the role of tumor-infiltrating B-cells and its impact on the survival in patients with PDAC remains controversial. We therefore aimed to assess the prognostic value of CD20-positive B-cells and CD20-positive B-cell aggregates as well as CD138, IgM, Pax5, and Ki67 on the survival of patients with PDAC using immunohistochemistry of FFPE pancreatectomy tissue sections from patients that underwent primary surgery for pT3-and R0-pancreatic adenocarcinoma between 1995 and 2016. Patients with PDAC were matched and grouped in 16 long-term-survivors (LTS, median overall survival (OS): 96 months [range: 61–177 months]) and 16 short-term-survivors (STS, median OS: 16 months [range: 7–32 months]). CD20-positive B-cells and B-cell aggregates in the tumor infiltration zone were significantly upregulated in the LTS-group compared to the STS-group (p = 0.0499 respectively p = 0.0432). Regarding the entire patient cohort (n = 32) CD20 positive B-cell aggregates in the tumor infiltration zone were an independent prognostic marker for overall survival in multivariate analysis (HR 9.2, CI 1.6–51.4, p = 0.012). These results underline the importance of tumor-associated B-cells for prognosis of patients with PDAC. The detailed role of B cells in the pathomechanism of PDAC should be further investigated for predicting outcome, identifying appropriate treatment regimens, and developing novel therapeutic options.
CRIS-Team Scopus Importer:2020-03-17
Keywords: B-cell aggregates; B-cells; CD20; Pancreatic ductal adenocarcinoma; Survival